Aerogel composition for thermal insulation

By using aerogel-containing compositions to manufacture flexible insulation members, the mechanical and thermal management challenges posed by battery expansion and contraction in electric vehicles are solved, achieving excellent thermal insulation and mechanical properties.

CN119907873APending Publication Date: 2025-04-29CABOT CORP
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202380066612.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-09
Filing Date
2023-09-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Rechargeable batteries in electric vehicles expand and contract during charging and discharging during vehicle life, resulting in mechanical and thermal management challenges for insulating spacers.

Method used

Flexible insulation members are made of aerogel-containing compositions, such as nonwoven blankets, and aerogel particles and fibrous components are combined through wet-laid technology, and polymers, IR sunscreens, flame retardants and other materials are added to form a thermal control product with excellent insulation and mechanical properties.

Benefits of technology

Good thermal insulation performance, mechanical robustness and compressibility of the insulating spacer are achieved, and can adapt to the expansion and contraction of the battery cell, reducing heat propagation and wear of the battery material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005314394380000471
    Figure BDA0005314394380000471
  • Figure BDA0005314394380000481
    Figure BDA0005314394380000481
  • Figure BDA0005314394380000641
    Figure BDA0005314394380000641
Patent Text Reader

Abstract

The aerogel composition comprises aerogel particles and a fibrous component, and the fibrous component comprises one or more materials selected from polymer fibers and inorganic fibers. The weight ratio of the aerogel particles to the fibrous component is (1: 3)-(10: 1). The aerogel composition further includes up to 25% by weight of a polymer, based on the total weight of the composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims priority to U.S. Provisional Application Nos. 63 / 407,202, filed on September 16, 2022, and 63 / 484,033, filed on February 9, 2023, the entire contents of both applications are incorporated herein by reference. Background Art

[0003] Aerogel particles can have very low density, high porosity and small pore size. Aerogels, and in particular silica aerogels, exhibit low density and low thermal conductivity, making them useful as insulating materials. Aerogels can be formed by removing solvent from hydrogels, for example by supercritical drying techniques or by solvent displacement combined with ambient pressure drying. Silica aerogels are typically hydrophilic, but can be rendered hydrophobic by using specific treating agents.

[0004] In the broadest sense, i.e. when considered as a "gel with air as dispersant", an aerogel is produced by drying a suitable gel. When used in this sense, the term "aerogel" includes aerogels in the narrow sense, such as xerogels and cryogels. If the liquid is removed from the gel starting at a temperature above the critical temperature and from a pressure above the critical pressure, the gel is designated as an aerogel in the narrow sense. In contrast, if the liquid is removed from the gel in a subcritical manner, e.g. forming a liquid-vapor boundary phase, the resulting gel is in many cases referred to as a xerogel. It should be noted that the gel according to the invention is an aerogel, meaning that it is a gel with air as dispersant.

[0005] Due to their excellent insulation properties, aerogels have been incorporated into various types of articles, including heat control articles (e.g., sheets, mats, or blankets) designed for applications such as construction, refrigeration, pipeline transportation, etc. One application that is gaining increasing attention involves the insulation of rechargeable batteries in electric vehicles (EVs).

[0006] US9399864 discloses a wet-laid aerogel blanket produced from a slurry of aerogel particles with a polymer binder. CN112430018 discloses a fiber paper impregnated with aerogel retained by a silica binder. CN112522949 discloses an aerogel blanket in which an aerogel slurry is injected into a glass fiber mat, which is then immersed in a slurry containing a polymer curing agent. CN112681009 discloses a double-layer paper system impregnated with an organic solution of silica aerogel. There remains a need for such a thin aerogel blanket that maintains thermal conductivity and tensile strength and has a reduced amount of components such as binders that can reduce thermal insulation properties and contribute to flammability. Summary of the invention

[0007] It has been found that insulative spacers for EV applications often encounter challenges associated with the tendency of battery cells to expand and contract during charging and discharging during the life of the vehicle.

[0008] Therefore, there is a need for ways to address at least some of the issues surrounding the insulation of rechargeable batteries in electric vehicles. Particularly desirable are insulation blankets that exhibit good thermal insulation properties and a variety of mechanical properties. For example, it is desirable that the insulating spacer have sufficient mechanical robustness to withstand the mechanical challenges of handling (e.g., during installation) and operation and that it may not be too rigid or incompressible.

[0009] Many embodiments described herein relate to thermal management articles that are flexible insulating members, such as nonwoven blankets, sheets, mats, felts, etc. The articles can be made from compositions comprising aerogel particles and other materials by wet-laid techniques.

[0010] In some embodiments, the aerogel composition comprises aerogel particles and a fibrous component, wherein the fibrous component comprises one or more materials selected from polymer fibers and inorganic fibers. The weight ratio of aerogel particles: fibrous component is 1:3-10:1. The aerogel composition further comprises up to 25 weight percent of a polymer based on the total weight of the composition.

[0011] The composition may further include materials such as IR opacifiers, flame retardants or flame retardants, heat absorbers, processing aids, etc. Binders, water, dispersants, emulsifiers, flocculants, etc. may be included as needed in the manufacture of thermal management articles.

[0012] The composition can be used, for example, to prepare nonwoven blankets, mats or other articles by a wet-laid process, and is believed to bring significant benefits to the finished product. Thus, the thermal control articles described herein can have excellent insulation properties, for example, thereby reducing heat propagation from a battery cell experiencing thermal runaway to adjacent cells or other battery components. The composition is preferably non-flammable, producing an article that will pass UL94-V0 testing or other flammability / combustibility testing.

[0013] Additional benefits imparted to the final article may include increased flexibility, compressibility, elasticity, tensile strength, and impact resistance. By allowing the battery encasement to expand and contract, these articles help mitigate the effects of dimensional changes in battery compartments (e.g., cells, modules, and packs), reducing the wear-and-tear that this type of cycling can cause on battery materials.

[0014] The above and other features of the present invention, including the various details of construction and the combination of parts, and other advantages, will now be described in more detail with reference to the accompanying drawings and pointed out in the claims. It should be understood that the specific methods and devices used to embody the present invention are shown in an illustrative manner and are not intended to be limiting of the present invention. The principles and features of the present invention may be adopted in a variety of embodiments without departing from the scope of the present invention. DETAILED DESCRIPTION

[0015] The present invention will now be described more fully hereinafter with reference to the accompanying drawings, in which illustrative embodiments of the present invention are shown. However, the present invention may be implemented in many different forms and should not be construed as limited to the embodiments set forth herein; on the contrary, these embodiments are provided so that this disclosure will be thorough and complete and will fully convey the scope of the present invention to those skilled in the art.

[0016] As used herein, the term "and / or" includes any and all combinations of one or more of the related listed items. In addition, all conjunctions used should be understood in the most inclusive sense possible. Therefore, unless the context clearly requires otherwise, the word "or" should be understood to have the definition of a logical "or" rather than a logical "exclusive or". In addition, unless otherwise clearly stated, the singular form and the articles "one", "a kind" and "the (said)" are intended to also include plural forms. It will be further understood that when used in this specification, the terms: include (includes), include (comprises), include (including) and / or contain (comprising) specify the existence of stated features, integers, steps, operations, elements and / or components (components), but do not exclude the existence or addition of one (kind) or more (kinds) of other features, integers, steps, operations, elements, components (components) and / or their groups. In addition, it should be understood that when an element including a component (component) or a subsystem is referred to and / or shown as connected or coupled to another element, it can be directly connected or coupled to another element or there can be intermediate elements.

[0017] It should be understood that although terms such as "first" and "second" are used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. Therefore, without departing from the teachings of the present invention, the element discussed below can be referred to as the second element, and similarly, the second element can be referred to as the first element.

[0018] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those of ordinary skill in the art to which the present invention belongs. It will be further understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the context of the relevant art, and will not be interpreted in an idealized or overly formal sense unless explicitly defined as such in this article. Unless otherwise indicated, all ratios and percentages are based on weight.

[0019] The present invention generally relates to a composition or heat control article containing aerogel (which can be a flexible member, such as a blanket, a sheet, a felt, a pad, to name a few). In one example, the article is a flexible nonwoven blanket. The aerogel composition includes aerogel particles and a fibrous component, wherein the fibrous component includes one or more materials selected from polymer fibers and inorganic fibers. The weight ratio of aerogel particles: fibrous component is 1:3-10:1. The aerogel composition further includes up to 25 weight percent of a polymer based on the total weight of the composition. The composition has a thickness of 0.3-6 mm, a thermal conductivity of up to 32 mW / mK at 25°C, a UL-94 rating of V0, a ​​tensile strength of 0.09-5 MPa, and a tensile strength of 0.1-0.6 g / cm 3 density.

[0020] In a specific implementation, the aerogel is a silica aerogel in the form of granules. Any type of silica aerogel particles can be used. The aerogel can be formed as described in US7470725. Suitable aerogels can be made of water glass or of organic materials such as TEOS and TMOS. In order to reduce the radiation contribution to thermal conductivity, the aerogel particles can be incorporated with IR opacifiers, such as carbon black, aluminum oxide, graphite, titanium dioxide, iron oxide, silicon carbide, zirconium dioxide or mixtures thereof. Aerogel particles can be obtained from a variety of sources, including from Cabot Corporation under the ENOVA and ENTERA brands and from JIOS Aerogel under the AEROVA brand.

[0021] The silica aerogel can have a particle size of 0.1-5 mm, such as 0.1-4 mm, 0.1-0.5 mm, 0.1-1 mm, 0.1-1.5 mm, or 1-4 mm. The aerogel can have a narrow or wide particle size distribution and can be in the form of a crushed powder. The diameter of the aerogel particles can be measured along the longest cross-section in a given particle, or the particle size range can be measured by screening.

[0022] Silica aerogel particles can be hydrophobic, exhibiting a water contact angle greater than 90 degrees. Commercially available examples of such aerogels are Brand of aerogel, brand aerogels and IC3110, P100, P150, and P200 aerogels, all from Cabot Corporation.

[0023] Some implementations utilize a mixture of silica aerogel and hydrophobic silica aerogel.

[0024] Aerogel particles are also commercially available as a mixture with an opacifier such as carbon black.

[0025] In some implementations, the aerogel particles have a porosity greater than about 60% and a density less than about 0.4 g / cc. In other implementations, the aerogel particles have a density of about 0.05 to about 0.15 g / cc.

[0026] The thermal conductivity of the aerogel particles at 25° C. may be less than about 40 mW / m·K, less than about 25 mW / m·K, or about 12 mW / m·K to about 18 mW / m·K, or lower. To reduce flammability, the aerogel particles may be low-calorie aerogels, such as those having, for example, a caloric content of less than 10 MJ / kg, less than 8 MJ / kg, less than 7 MJ / kg, or less than 6 MJ / kg.

[0027] Since the aerogel is preferably preformed (prepared prior to making the thermal control article containing the aerogel), any desired aerogel structure, morphology or other properties can be selected and generally maintained in the final product. The amount of aerogel in the composition or heat control member can be 15-65 wt%, such as 20-60 wt%, 25-55 wt%, 30-50 wt%, or 35-45 wt%.

[0028] In addition to the aerogel component, the compositions described herein further include one or more other ingredients. In many cases, these ingredients or components are selected to give the final product (e.g., a blanket) a specific function and / or property. In some cases, the type and / or amount of the added component is selected to achieve a balance or compromise between the desired contribution and the less desired contribution that the component may make to the final product. When selecting the type and / or amount of the component to be used, manufacturing parameters, final application or other factors may be considered.

[0029] When added to aerogels, components that can affect the performance of the finished product are fibrous materials. Relative to the total weight of the aerogel composition or thermal control product, the fibrous material can be present in an amount of 5-55% by weight, such as 10-50% by weight, 15-40% by weight, 20-35% by weight, or 10-30% by weight. Specific implementations utilize fibrous components including temperature-resistant polymeric fibers and / or inorganic fibers. Exemplary inorganic fibers include ceramic wool, ceramic fibers, and glass fibers. Examples of polymeric fibers include polybenzimidazole (PBI), aromatic polyamides (aramids), or any combination thereof.

[0030] Whereas ceramic fibers are typically made by a drawing process and then cut to the desired length, ceramic "wool" (or other types of wool, such as mineral wool, sometimes also called "stone" wool) are usually made by melt spinning. In general, cotton tends to have longer, more tangled fibers. Individually, cotton fibers may not be stronger than shorter ceramic fibers (made by drawing and chopped). However, in bulk, cotton can have an additive effect that can improve the mechanical integrity of the composition and / or thermal management article.

[0031] In many cases, the diameter of cotton fibers ranges from about 1 micrometer (μm) to several hundred micrometers. The fiber length can range from about 100 μm to several hundred μm or longer, sometimes hundreds of millimeters (mm) long.

[0032] These high aspect ratio cottons also have the effect of improving drainage and retention in wet-laid products because they provide additional surface area for well-dispersed active materials to accumulate during the agglomeration process. This reduces the amount of active material that is removed with excess process water during the forming process.

[0033] The amount of ceramic wool that can be used will generally depend on the desired properties (e.g., tensile strength, tear resistance, impact resistance), intended use, and / or other factors. Ceramic wool can be provided in an amount within the range of 0.5-100% by weight (relative to the weight of the fibrous component used to prepare the composition). In illustrative examples, it is present in an amount within the range of about 5-about 30% by weight. For example, it can be present in the fibrous component in an amount of about 10-about 20% by weight.

[0034] Relative to a finished product, such as a carpet, the ceramic wool may be present in the final product in an amount in the range of 0.25 wt %-4 wt % of the weight of the article, such as about 0.5 to about 2 wt %, such as in the range of about 0.5 to about 1.0 wt %; about 0.5 to about 1.5; about 0.5 to about 2.0 wt %; or about 1.0 to about 1.5; about 1.0 to about 2 wt %; or about 1.5 to about 2.0 wt %.

[0035] Suitable ceramic wool includes aluminum (provided as Al2O3), silicon (in the form of SiO2) and iron (in the form of Fe2O3) or any combination of these. In addition to or in place of any of these components, some ceramic wools may also include titanium dioxide (TiO2).

[0036] Although not a required element, the presence of zirconium can provide mechanical benefits and / or can contribute to the temperature resistance of the final aerogel composition and / or thermal management article (e.g., blanket). In some implementations, zirconium (typically in the form of zirconium oxide (ZrO2) is provided in a zirconium-containing wool, which may also include other elements such as aluminum, silicon, iron and / or titanium. Commercially, Ceramaterials (Dingmans Ferry, PA) offers two types of spun fibers, one with a higher zirconium oxide concentration (temperature resistance up to 2600°F / 1400°C) and one with a lower zirconium oxide loading (2300°F / 1400°C).

[0037] In the finished product, the blanket (e.g., ceramic wool) can be identified by analytical techniques, such as high-resolution microscopic examination of a uniform cross-section of a sample product (e.g., blanket). It is believed that even after processing operations, the ceramic wool will maintain a differentiated configuration compared to chopped ceramic fibers. Other techniques that may be applicable include scanning electron microscopy (SEM) using energy dispersive X-ray (EDX) capabilities (often abbreviated as "SEM / EDX"), which associates typical concentrations of elements with ceramic wool to distinguish it from other types of fibers.

[0038] Another type of wool that can be used to prepare the compositions described herein is mineral wool (also referred to in some cases as "stone" wool). Mineral wool is available from Rockwool A / S under the trade name Mineral wool is commercially available, commercially available from Knauf Insulation (Shelbyville, IN, USA), and commercially available from other suppliers. The amount of mineral wool can be the same or similar to that used in the case of ceramic wool. However, other ranges can be used.

[0039] Mineral wool can be identified in a finished product (e.g., carpet) by techniques such as scanning electron microscopy (SEM) using energy dispersive X-ray (EDX) capabilities (often abbreviated "SEM / EDX"), which associates typical concentrations of elements with mineral wool to distinguish it from other types of fibers.

[0040] In some embodiments, the compositions described herein include various forms of temperature resistant polymeric materials. Some methods utilize aramid fibers that can be defined as "pulp" (between 0.1-6 mm) or short cut fiber (>6 mm). Aramid short cut fiber and pulp are widely available, with the major global manufacturers being Dupont (under the trade name ). Alternatively, or in addition, longer aramid fibers cut to lengths such as 3 mm, 6 mm, or 12 mm may also be used.

[0041] Other methods utilize polybenzimidazole (PBI) fibers, which are typically characterized by excellent heat and chemical resistance. Since PBI fibers have no discernible melting point, they will not catch fire or drip when exposed to high temperatures. PBI fibers are available from PBI Performance Products (Charlotte, NC). PBI fibers can be at least .1 mm long, such as 0.5-10 mm, 1-8 mm, or 2-6 mm.

[0042] It is believed that materials such as aramid or PBI fibers are particularly useful for addressing the expansion and contraction observed in battery packages that are charged or discharged under hot or cold conditions. Allowing the battery encasement to expand relieves pressure on the battery compartment, reducing wear and tear on battery materials.

[0043] While still imparting these advantageous properties, these polymeric fibers are typically used in the lowest possible amounts because their addition can compromise the desired low flammability rating of the finished product (eg, carpet).

[0044] PBI and / or aramid fibers can be provided in an amount ranging from about 0.5 to 100 wt % (relative to the weight of the fibrous component used to prepare the composition). In illustrative examples, they are present in an amount ranging from about 5 to about 30 wt %, or 25 to 80 wt %. For example, they can be present in the fibrous component in an amount ranging from about 10 to about 20 wt %.

[0045] In many cases, fibers such as aramid or PBI are used in an amount within the range of 0.25-4% (based on the weight of the aerogel composition or thermal management article), such as about 0.5-about 2% by weight, such as about 0.5-about 1.0% by weight; about 0.5-about 1.5% by weight; about 0.5-about 2.0% by weight; or about 1.0-about 1.5% by weight; about 1.0-about 2% by weight; or about 1.5-about 2.0% by weight.

[0046] In a finished product (eg, a carpet), aramid or PBI fibers can be identified by techniques such as SEM / EDX to distinguish the polymeric structure from the surrounding inorganic environment.

[0047] Ceramic fibers are known for their good oxidation resistance at high temperatures as well as good corrosion resistance. Typically, ceramic fibers are characterized by a polycrystalline (rather than amorphous) structure. Some (e.g., refractory ceramic fibers) are particularly useful as thermal insulation materials for high temperature applications. In some embodiments, ceramic fibers represent the majority component (greater than 50% by weight relative to the total weight of the fibrous components).

[0048] Suitable chopped ceramic fibers that can be used in the compositions described herein include one or more (two, three, four or more) inorganic oxides, such as Al2O3, B2O3, Na2O, K2O, CaO and MgO. Some fibers may also include silicon oxides. Many types of ceramic fibers (usually well characterized in composition, length and / or other properties) are commercially available. Suitable chopped ceramic fibers include, but are not limited to, 7000 and 6000 series fibers from Unifrax. In one example, the ceramic fiber is a rough-cut high-purity alumina-silica product from Unifrax. Ceramic fibers can have various diameters, such as 1.5-2.5 microns, and can be cut into specific lengths or obtained in uneven lengths, including a mixture of shot (unfiberized material) and longer fibers. In some embodiments, the collection of ceramic fibers may contain up to 45-55% shot. For the purposes of the present disclosure, shot (when present) is still considered to be part of the fibrous material in the aerogel composition or thermal control member.

[0049] Alternatively, or in addition, glass or other fibers may be used alone or in combination with one or more of the above-mentioned ceramic fibers and / or ceramic wool, aramid and / or PBI fibers. Exemplary glass fibers include: borosilicate (B fibers), acid-resistant borosilicate (C fibers), and calcium aluminoborosilicate (E fibers), which can be obtained, for example, from Lauscha Fiber International or Unifrax; and / or fibers consisting essentially of silica (Q fibers), which can be obtained, for example, from Johns Manville. The glass fibers can be cut into various lengths, such as 3 mm, 6 mm, or 12 mm, or can be used as "shot". The glass fibers can have various diameters from 0.25 microns to 12 microns, such as 0.25 microns to 0.5 microns, 0.5-1.5 microns, 1.5-2.5 microns, 1 micron to 5 microns, or 8 microns to 12 microns, such as 6, 9 or 12 microns. Alternatively, or in addition, more than one type of glass fiber may be used, for example cut to more than one length or diameter, such as a blend of fibers having a diameter less than 1 micron and fibers having a diameter greater than 5 microns. Silica gel fibers are produced by spinning gelled silica sol, for example, as described in US20200308729, the entire contents of which are incorporated herein by reference.

[0050] Other fibers that may be added to the ceramic fibers, glass fibers, ceramic wool and / or polymeric fibers (e.g., PBI or aramid) include non-ceramic fibers such as cellulose, cotton, carbon, acrylic, polyvinyl alcohol (PVA), phenolic, polyolefin and / or other types of fibers, as well as mixtures of such fibers.

[0051] The fibers employed may have any configuration known to those skilled in the art. For example, the fibers may have the form of chopped fibers, microfibers, woven fibers or nonwoven fibers.

[0052] The shape of the fiber cross section can be circular, polygonal, trilobal, pentaphallic, octal, strip, fir-tree, dumbbell or other shapes. Fiber can have consistent or variable diameter along the length of fiber. Hollow fiber can be used in some embodiments. In addition, fiber material can be smooth or wrinkled, and can be curled or straight.

[0053] In some embodiments, coated fibers are employed. Polyester fibers metallized with a metal such as aluminum are one example.

[0054] Fibers modified by additives are also suitable. Examples of such additives include, but are not limited to, antistatic agents such as carbon black, and / or IR opacifiers (typically used to reduce the radiative contribution to thermal conductivity), such as carbon black, titanium dioxide, aluminum oxide, iron oxide or zirconium dioxide, silicon carbide, or any mixture thereof.

[0055] In addition to including IR opacifiers, the radiative contribution to thermal conductivity can be further reduced by using blackened fibers, such as polyester fibers blackened with carbon black or simple carbon fibers.

[0056] The amount of the fibrous component (a fiber or a blend of fibers) used depends on its density, diameter, length, etc., and may be 1% to 99% by weight, preferably 5% to 55% by weight, such as 10% to 50% by weight, 15% to 40% by weight, 20% to 35% by weight, or 10% to 30% by weight, relative to the weight of the aerogel composition. In a specific embodiment, the mass ratio of the aerogel component to the fibrous component is in the range of 1:3 to 10:1 by weight, such as 1:2 to 10:1, 1:3 to 3:1, 1:2 to 2:1, 1:1 to 10:1, 1.2:1 to 9:1, 1:2 to 9:1, or 1:1 to 5:1. When the relative amount of the fibrous component is too large, the thermal conductivity of the aerogel composition and / or the thermal control article may be too high. When the relative amount of the fibrous component is too small, the tensile strength of the aerogel composition and / or the thermal control article may be too low.

[0057] Blends of fibers may also be used. For example, a first fiber selected to provide mechanical strength may be used in combination with a second fiber that is used to hold the aerogel and other particulate matter (e.g., sunscreen) in the blanket. The first fiber is typically a glass or ceramic fiber, while the second fiber is typically a fiber with a higher aspect ratio but may be a longer glass or ceramic fiber. Alternatively, or in addition, a third fiber may be included to enhance specific mechanical properties. For example, adding a polymer fiber as a third fiber may enhance the flexibility of the aerogel blanket.

[0058] Although the cotton and / or heat-resistant polymer fibers described herein may represent all fiber components in the composition, they are usually used in combination with glass or ceramic fibers. In many cases, glass or ceramic fibers can actually represent the main fibrous component (relative to the total weight of the fibrous component, greater than 50% by weight) and can be considered as the "main" fiber used in the composition. In such a case, the term "minor" can be applied to ceramic cotton and / or heat-resistant polymer fibers (e.g., PBI, aramid) in the composition. Alternatively, PBI or aramid fibers can represent the main fibrous component. Alternatively, or in addition, blends of glass and ceramic fibers (e.g., ceramic or glass as the main fiber and the other as the minor fiber) can also be used, and, generally, any fiber or cotton disclosed herein can be combined with one or more of the others. In certain embodiments, the weight ratio of the primary fiber to the secondary fiber is 100:1-1:100, for example, 50:1-1:50, 35:1-1:35, 25:1-1:25, 15:1-1:15, 10:1-1:10, 7:1-1:7, 5:1-1:5, 4:1-1:4, 3:1-1:3, or 2:1-1:2. In a specific implementation, glass or ceramic fibers are used alone or with aramid fibers in a weight ratio of 1:4-10:1, for example, 1:3-5:1, 1:2-3:1, or 1:1-2:1. Alternatively, or in addition, different types of glass fibers (e.g., glass fibers of 5-10 microns in diameter) are used in combination with glass microfibers of less than 1 micron in diameter in a weight ratio (larger diameter: smaller diameter) of 5:1-1:5 (e.g., 4:1-1:4, 2:1-1:2, or 1:5-1 to 1:1.5). Alternatively, or in addition, ceramic microfibers are primary fibers and glass fibers or microfibers are secondary fibers. Alternatively, or in addition, a combination of three or more types of fibers are used, for example, ceramic microfibers (less than 5 microns in diameter, or less than 3 microns in diameter) are used in combination with two or more of glass fibers of 5-10 microns in diameter, glass fibers of less than 5 microns in diameter, or less than 1 micron in diameter, aramid fibers, and PBI fibers. Alternatively, or in addition, the glass fibers used to make the aerogel composition or thermal control member are chopped to 6 microns or less or 3 microns or less.

[0059] The length and diameter of the fibers (e.g., glass or ceramic fibers) can vary with the specific application. Finer fibers such as microfibers (less than 5 microns or less than 1 micron in diameter) can, for example, increase flexibility, while the length and / or distribution of the fibers can play a role in increasing the mechanical strength of the final product (e.g., a blanket). In illustrative examples, the fibers are cut into lengths of 3 mm, 6 mm, or 12 mm or other commercially available lengths. Two or more different types of fibers or fibers made of the same material but characterized by different fiber lengths, length distributions, diameters, or diameter distributions can be used to obtain a bimodal or multimodal length or diameter distribution of the fibers.

[0060] In some embodiments, the composition comprises elastomeric particles, such as silicone particles, rubber powder or thermoplastic microspheres. It is believed that such materials potentially improve both the reinforcement and elasticity of the finished product (e.g., blanket). The elastomeric particles can be solid, hollow and / or resin-coated. For the purposes of this specification, the elastomeric powder or particles are classified together with other granular components of the composition, such as sunscreens, rather than being classified together with polymeric components such as dispersants, surfactants, flocculation aids, defoamers and adhesives.

[0061] Silicone powders or particles of various average particle sizes (average PS), for example in the range of about 1 micron to 1 mm in diameter, are commercially available. As an example, suppliers such as Shin Etsu Silicones offer suitable elastomer particles in its Silicone Powder KMP series. For example, particles with an average PS of 13 μm can be obtained under product code KMP-598, while product KMP-402 provides PS=30 μm.

[0062] Suitable amounts that can be used can be determined considering desired properties, manufacturing parameters, and / or other factors. In some implementations, the silicone particles are provided in a ratio of up to 1:1 relative to the aerogel component, for example, 1:10-1:1, 1:8-1:2, or 1:6-1:3.

[0063] Silicone rubber particles can be used in combination with one or more inorganic fibers and / or cotton and / or temperature-resistant polymer fibers as described herein. For example, they can be combined with aerogel particles, with one or more inorganic fibers, and / or one or more of ceramic wool, aramid fibers, and / or PBI fibers. Alternatively, organosilicon particles can be used in compositions that do not include ceramic wool or polymer fibers such as aramid or PBI.

[0064] In many embodiments, the compositions described herein include an opacifier, such as an infrared (IR) opacifier, to reduce radiative heat transfer. These materials reduce the transmission of infrared radiation and can include, for example, carbon black, mica, aluminum oxide, graphite, titanium dioxide, rutile sand, iron oxide, silicon carbide (SiC), graphite, or zirconium dioxide. Some suitable types of titanium dioxide include, for example (DuPont) and (Huntsman). IR sunscreens can be used alone or as a mixture of two or more compounds. The size of the particles can be selected to reflect a specific wavelength. For example, for ceramic sunscreens such as titanium dioxide, particles smaller than 1 micron (measured by laser diffraction) can block visible light more effectively than IR radiation, while the thermal conductivity of the particles can be increased at larger particle sizes (e.g., greater than 3 microns). In another example, silicon carbide (Federation of European Producers of Adhesives) with a grit size of F230 to F2000 is available, for example, F500, F600, F800, F1000, F1200 and F1500.

[0065] IR sunscreens can be added in selected amounts to provide a target level of IR transmission reduction in an aerogel composition and / or thermal control article (e.g., blanket). Exemplary such levels can be, for example, up to 10%, 0.5-8%, 0.75-5%, or 1-3% sunscreen based on the total mass of the aerogel composition and / or thermal control article. Adding sunscreens characterized by two or more different average particle sizes in a given composition can extend the range of IR wavelengths covered.

[0066] In some embodiments, the aerogel composition and / or the thermal control article (e.g., blanket) may include a flame retarder or flame retardant. The flame retarder may be, for example, an alkali oxide, an alkaline earth oxide, aluminum trihydrate, magnesium hydroxide, antimony oxide, titanium dioxide, rutile sand, melamine compounds, phosphate-based or halogen-based compounds. In a particular embodiment, the titanium dioxide particles may have a diameter of about 1.18 μm, 0.9-1.3 μm, 0.8-1.4 μm, or 0.5-4.0 μm as measured by laser diffraction, and in certain embodiments, the particle size distribution may have a d50 of about 1.0 μm + / - 0.01 μm, + / - 0.02 μm, or + / - 0.05 μm. Halogenated flame retardants include, for example, brominated flame retardants (BFRs), such as organic bromide compounds, including polymeric organic bromide compounds. In another set of embodiments, the polymeric flame retardant has a structure with a high ratio of heteroatoms to carbon atoms. For example, in some embodiments, the ratio of heteroatoms to carbon atoms can be greater than 0.5:1, greater than 1:1, or greater than 2:1, and in specific embodiments, the heteroatoms can be nitrogen and / or sulfur. The flame retardant and / or flame retardant can be incorporated into the aerogel composition and / or thermal control article at a concentration sufficient to inhibit flammability or meet specifications such as UL94-V0. Alternatively, or in addition, exemplary aerogel compositions and / or thermal control articles can display, for example, a heat content of less than 10MJ / kg, less than 8MJ / kg, less than 5MJ / kg, less than 3MJ / kg, less than 2MJ / kg, or less than 1MJ / kg, such as 0.5MJ / kg or 1MJ / kg to 5MJ / kg.

[0067] The concentration of the flame retardant and / or flame retarder that can be used can be in the range of 0.1-5.0 wt%, 0.2-2.0 wt%, and 0.3-1.5 wt% relative to the mass of the aerogel composition and / or thermal control article. In a specific implementation, the flame retarder or flame retardant is combined with aerogel particles, for example, a mixture combined with silica aerogel.

[0068] Endothermic materials may also be used. Such materials help the aerogel composition and / or thermal control article (e.g., blanket) to behave not only as an insulator, delaying heat transfer, but also as a heat reservoir that can store thermal energy. Such endothermic materials may include aluminum hydroxide and other materials known to those skilled in the art. Alternatively, or in addition, the endothermic material may include a phase change material that stores heat by undergoing a thermodynamic phase change or a change in hydration state or crystal structure. Suitable phase change materials include both organic materials and inorganic materials (e.g., metals, inorganic salts, and inorganic hydrated salts). The endothermic material may be combined with aerogel particles and / or hydrophobic silica aerogel, or may be deposited on the surface of the aerogel pores or otherwise impregnated into the aerogel pores.

[0069] The composition may optionally include a binder. In some cases, the binder may help prevent the widespread dispersion or dissipation of silica aerogel, hydrophobic silica-containing particles, and / or other particulate components of the aerogel composition and / or thermal control article to prevent catastrophic failure or explosion of isolated items (e.g., batteries). Examples of suitable binders include, but are not limited to, silicones, polyurethanes, epoxies, polyvinyl alcohols, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, acrylate (acrylic) polymers, and the like. Preferably, the binder includes a heat-resistant and / or flame-retardant polymer. Binders such as polyvinyl alcohol, silicones, polyurethanes, styrene butadiene polymers, or acrylates or acrylic polymers may also bond additives such as carbon black to aerogel particles to reduce dusting during downstream processing of the aerogel composition. Exemplary commercially available adhesives include Joncryl FLX5201, FLX5220, FLX5026A and 1670 polymers from BASF, U4000, U4101 and APU 10120 polymers from Alberdingk Boley, Novacryl PSR300 polymer from Synthomer, and Styrofan 4306 polymer from BASF. The adhesive may be mixed with some or all of the components of the mixture (including any additives incorporated into the mixture) using an impeller or other suitable equipment known to those skilled in the art. Preferably, the adhesive does not make the aerogel blanket flammable under UL 94 or other flammability test methods.

[0070] Processing aids may also be included. The processing aid selected will depend on the manufacturing method and form of the aerogel composition and / or thermal control article. Suitable processing aids include, but are not limited to, defoamers, surfactants, dispersants, and emulsifiers.

[0071] Various commercial defoamers are known to those skilled in the art and are suitable for use with the aerogel compositions herein. The defoamer can be a polyol or a polyglycol, such as can be purchased from Evonik Industries under the name Surfynol. Selectable polyols include, but are not limited to, 1,3-propylene glycol, 1,2-butylene glycol, 2,3-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, glycerol, trimethylolpropane, pentaerythritol, triethanolamine, and trishydroxymethylaminomethane. Alternatively, or in addition, an oil-based or fatty acid-based defoamer can be used. Alternatively, or in addition, the defoamer can be a polymer-based defoamer, such as a silicone-based defoamer, such as Dehydran 1293 defoamer from BASF.

[0072] Dispersants or surfactants can be selected from, for example, ionic (anionic and cationic) surfactants and dispersants, amphoteric surfactants and dispersants, nonionic surfactants and dispersants, and high molecular weight surfactants and dispersants. Suitable anionic surfactants include alkyl sulfates and higher alkyl ether sulfates, more specifically, such as ammonium lauryl sulfate and polyoxyethylene lauryl ether sodium sulfate. Suitable cationic surfactants include aliphatic ammonium salts and amine salts, more specifically, such as alkyl trimethyl ammonium and polyoxyethylene alkylamine. Amphoteric surfactants can be betaine type, such as alkyl dimethyl betaine, or oxido type, such as alkyl dimethyl amine oxido.

[0073] Suitable nonionic dispersants include, for example, glycerol fatty acid esters, propylene glycol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitan tetraoleate, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxypropylene alkyl ethers, polyethylene glycol fatty acid esters, higher fatty acid alcohol esters, polyol fatty acid esters, polyether-modified polydimethylsiloxanes, and the like.

[0074] Additional potential surfactants include AEROSOL OT (sodium di-2-ethylhexyl sulfosuccinate), BARLOX 12 (branched alkyl dimethyl amine oxide), BARLOX 12i (branched alkyl dimethyl amine oxide), TRITON 100 (octylphenoxypolyethoxy (9-10) ethanol), TWEEN surfactants such as TWEEN 100 surfactant, and BASF pluronic surfactants. Other examples of wetting agents include glycols, alkoxylated polyoxyalkylene fatty ethers, such as polyoxyethylene fatty ethers, sorbitan esters, mono- and diglycerides, polyoxyethylene sorbitan esters, polymeric surfactants such as Hypermen polymeric surfactants, sodium coco-PG-dimonium chloride phosphate and coamidopropyl PG-dimonium chloride phosphate, phosphate esters, polyoxyethylene (POE) fatty acid esters, Renex nonionic surfactants (nonionic esters formed by the reaction of ethylene oxide with unsaturated fatty acids and heterocyclic resin acids), alcohol ethoxylates, alcohol alkoxylates, ethylene oxide / propylene oxide block copolymers, polyoxyethylene derivatives of sorbitan esters, or combinations thereof. Preferred dispersants have at least one cationic or cationizable group and an HLB ratio of 2-20, more preferably oligomers of ethylene oxide and propylene oxide having a molar ratio of ethylene oxide mers to propylene oxide mers of 0.1:1 to 11:1. Exemplary dispersants include, but are not limited to, Jeffamine M-2070 compound (Huntsman) (a monofunctional primary amine having a weight average molecular weight of about 2,000, a propylene oxide / ethylene oxide (EO / PO) molar ratio of 31 / 10, and an HLB value of 13.8), Jeffamine M600 compound (Huntsman) (a monofunctional primary amine having a weight average molecular weight of about 600, a propylene oxide / ethylene oxide (EO / PO) molar ratio of 1 / 9, and an HLB value of 2), Jeffamine ED900 compound (Huntsman) (a difunctional primary amine having an EO / PO ratio just greater than 2 and a weight average molecular weight of about 900), Surfonamine L-300 compound (Huntsman) (a monofunctional primary amine having an EO / PO ratio of about 58 / 8, a weight average molecular weight of about 3000, and an HLB value of about 17.1), and Surfonamine B-200 compound (monofunctional primary amine having an EO / PO ratio of about 6 / 29 and a weight average molecular weight of about 2000).

[0075] While in many cases the ingredients can be combined in any suitable manner, techniques for incorporating some components may benefit from additional considerations. For fibers, for example, too little mixing energy can result in undispersed fiber bundles that are not effective in improving performance. On the other hand, over-dispersion (at unrestricted mixing length or mixing energy) can result in self-entanglement and "balling." Too much chopping and cutting energy can result in a reduction in fiber length to less than the ideal length, thereby affecting product attributes or performance. As for equipment, it has been found that mixing operations that rely on cutting blades (vanes) with sharp leading edges can also contribute to fiber length reduction. While this may be relatively benign on a short time scale, the effect is expected to accelerate over longer time periods.

[0076] It has also been found that certain properties of the material being incorporated can make the material more susceptible to the effects of "overprocessing". In the case of fibers, for example, for fiber lengths greater than about 6 mm (0.25 inches) and / or fine coarseness, such effects become more pronounced.

[0077] Thus, some embodiments described herein involve controlling some mixing parameters, such as mixing time, energy applied, equipment type, such as blade type. In specific examples, the mixing parameters take into account the properties of the material being processed. In other examples, the properties of the material are evaluated and then associated with appropriate mixing parameters. Establishing appropriate mixing parameters can be based on routine experimentation, prior experience, etc.

[0078] To form the compositions described herein, the ingredients may be combined in any suitable manner and may involve a single step. However, in many cases, mixing is performed in a sequence of two or more steps using equipment known in the art. In one example, aerogel particles and fibers are added to a solution containing a processing aid such as a defoamer, a surfactant, a dispersant, and / or an emulsifier.

[0079] The thermal control article may take any form known to those skilled in the art. For example, an aerogel composition such as a blanket or mat containing fibers may be manufactured using techniques such as those described in US9399864, US20210363699, WO2022024085, CN112759353, US11274044, CN112681009, CN113943171, CN110093783, CN112681009, JP2015048543 and / or US20200295328, all of which are incorporated herein by reference.

[0080] Typically, in a "wet-laid" process, aerogel particles and optional materials are flocculated from an aqueous slurry to form a substantially stable uniform suspension of particles (flocs). Preferably, the aqueous slurry includes less than 5% by weight of organic solvent, such as less than 3% by weight, or less than 1% by weight of organic solvent. The flocs can be separated from the water-based solvent to form a two-phase system consisting of flocculated aerogel particles and a substantially aqueous supernatant. The flocs can float on the top of the supernatant, or a portion of the flocs can be suspended in the supernatant. The flocculated material can support a uniform distribution of different particles from which a blanket can be made. This stable, consistent distribution of particles can provide an aerogel blanket that exhibits a uniform composition throughout the process.

[0081] In one embodiment, as described in US9399864, an aqueous slurry is prepared with a mixture of silica aerogel, hydrophobic silica-containing particles, ceramic fibers, and other components (e.g., adhesives, sunscreens, flame retardants, defoamers, etc.). Preferably, the relative amounts of the various components in the aqueous slurry correspond to their relative amounts in the aerogel composition. A charged compound or other emulsifier or dispersant is included in the slurry to produce an emulsion, which is then coagulated with a flocculant. The resulting floccules are collected on a scrim or belt and dehydrated. The thickness of the aerogel composition can be adjusted by increasing or decreasing the solid loading of the aqueous slurry. In some embodiments, the solid loading can be 5-25% by weight of the aqueous slurry, such as 5-10% by weight, 10-15% by weight, 15-20% by weight, or 20-25% by weight.

[0082] Without being bound by any particular theory, it is believed that as flocculation becomes more effective, the aerogel particles are able to pack more densely in the blanket. The flocculant is preferably able to flocculate enough solids in the mixture so that most of the solids float to the top of the aqueous mixture, making the aqueous medium relatively clear rather than turbid. Preferred flocculants are polymeric flocculants as compared to inorganic flocculants. Exemplary polymeric flocculants include quaternary polyamines, for example, polyamines (e.g., from Kemira 577 or 581 flocculants), and polyacrylamides (e.g., Nalclear 7768, Nalclear 8187, and Nalclear 8176 polymers from Nalco), dicyandiamide resins, polydiallyldimethylammonium chloride (PDADMAC), aminosilanes, quaternary amine functionalized silanes, silicone resins, and mixtures or emulsions of any of these. In some embodiments, the flocculant has the form of an aqueous emulsion or latex of the flocculant. The flocculant may have various number average molecular weights, for example 400-60,000,000, preferably 400-1,000,000, such as 5000-10,000, 10,000-100,000, 100,000-500,000, 500,000-1,000,000, 20,000-10,000,000, 1,000,000-30,000,000 or 5,000,000-50,000,000.

[0083] Flocculants can be used in combination with flocculating polymers. Flocculants are preferably ionic polymers; flocculating polymers are preferably ionic polymers of opposite charge. In some embodiments, the flocculating polymer has the form of an aqueous emulsion or latex of the flocculating polymer. The flocculating polymer may have a number average molecular weight of 400-1,000,000, such as 5000-10,000, 10,000-500,000, 20,000-50,000, or 50,000-1,000,000. Alternatively, the flocculating polymer may have a molecular weight within the range described above for the flocculating agent. Suitable flocculating polymers include, but are not limited to, natural and synthetic latex polymers, acrylics, and polyacrylamides. Since the flocculant is preferably a charged polymer, any agent listed above as a flocculating agent may also be used as a flocculating polymer, depending on the relative charge. Importantly, only one component of the flocculation system (referred to herein as the flocculation polymer) is added to the aqueous slurry prior to or concurrently with the addition of the other components (aerogel, fibers, opacifier, etc.), and the flocculant is added only after all other components are combined. Preferably, the flocculant and the flocculation polymer are used in amounts such that the amount of charge provided by the flocculant (i.e., charge density multiplied by mass) does not deviate more than 20% from the amount of charge provided by the flocculation polymer, such as not more than 10%, not more than 5%, or not more than 1%.

[0084] The total amount of flocculant and flocculating polymer together should be sufficient to bind the various components of the aerogel composition, but should not be so large that they fill the pores of the aerogel composition, thereby reducing thermal conductivity. In fact, in certain embodiments, the flocculant and flocculating polymer can provide all the bonding functions required in the aerogel composition, thereby avoiding the use of adhesives. The use of flocculants and flocculating polymers in amounts greater than necessary may also undesirably affect the mechanical properties of the composition, undesirably increase density, increase the heat content of the aerogel composition, or reduce flammability. The total weight fraction of polymers (including dispersants, adhesives, defoamers, flocculants and flocculating polymers) used to produce the aerogel composition can be less than 25%, such as 3-25%, such as 4-10% by weight, 10-15% by weight, 15-20% by weight, or 20-25% by weight, based on the total weight of the materials added to the aqueous solvent, i.e., the total weight of the materials in the floccules and supernatant, but excluding the aqueous solvent. In the case where no binder is used, the amount can be even smaller, such as 3-15 wt%, or 8-17 wt%, based on the total weight of the materials added to the aqueous solvent to form the aerogel composition. The same proportion of polymers can be found in the resulting aerogel composition. Similarly, the total weight of polymers (including dispersants, binders, defoamers, flocculants and flocculating polymers) in the resulting aerogel composition can be less than 25%, such as 3-25%, such as 4-10 wt%, 10-15 wt%, 15-20 wt%, or 20-25 wt%, based on the total weight of the aerogel composition. In the case where no binder is used, the amount can be even smaller, such as 3-15 wt%, or 8-17 wt%, based on the total weight of the aerogel composition.

[0085] Threshold amounts of dispersants, defoamers, flocculants, and flocculating polymers are required to form a cohesive aerogel composition using a wet-laid process. Those skilled in the art will recognize that the amounts required will vary depending on the relative amounts of the non-polymer components (aerogel, fiber, sunscreen, flame retardant, endothermic material, etc.). However, excess material may be detrimental to thermal conductivity and / or flame retardancy according to UL-94, and may undesirably increase density. In certain embodiments, the total amount of flocculation system (i.e., flocculant and flocculating polymer) and binder used to produce an aerogel composition or thermal control article is 3-20% by weight, such as 4-16% by weight, based on the total weight of the materials in the floccules and supernatant, but excluding aqueous solvent. Similarly, the total amount of flocculation system and binder in the aerogel composition may be 3-20% by weight, such as 4-16% by weight, based on the total weight of the aerogel composition.

[0086] In certain embodiments, the packing density of the various components can be increased by using compression to squeeze out additional water from the flocculate before drying. For example, the flocculate can be pressed through a double roller press or between two plates or press plates. Alternatively, a single roller can be passed over the flocculate. Pressing increases the packing density of the various components by squeezing water out of the flocculate. In the final product, this reduces the porosity between the particles because the remaining water is replaced by air during drying. Alternatively, or in addition, any of these methods can be used to compress the aerogel composition after the aerogel composition is dried. After drying, compression can be used to make the composition thinner and denser, thereby allowing the aerogel composition and / or thermal control member to occupy less space and also improve mechanical properties. The density of the aerogel composition or thermal control member can be 0.1-0.6g / cm 3 , for example 0.15-0.5 g / cm 3 , 0.15-0.4g / cm 3 , or 0.2-0.35g / cm 3 .

[0087] In another embodiment, fiber, aerogel, adhesive, and any other desired components are loaded into a mold and pressed into a pad, for example, as described in EP3835262, the entire contents of which are incorporated herein by reference. It may be necessary to heat or otherwise activate the polymeric adhesive in the mold. Alternatively, or in addition, fiber, aerogel, adhesive and other components can be formulated into a paste and extruded, for example, as in EP3835262 and WO2020228998, the entire contents of which are incorporated herein by reference. Alternatively, using techniques such as those described in CN113785431, CN110544809, JP2012145204 and / or US20210332932, fiber, aerogel and any other desired components are used to fill envelopes (envelope) or other cavities, all of which are incorporated herein by reference. Alternatively, or in addition, the mixture may be incorporated into or combined with a polymer foam, for example as described in WO2020211320, JP2020019925, US10640629.

[0088] Thermal control articles (e.g., blankets) comprising aerogel compositions can be manufactured in a generally planar or flat form for insertion between unit cells of a rechargeable battery (e.g., a lithium-ion battery). In other approaches, the article can be prepared into another desired shape. For example, the thermal control article can be shaped to be disposed around a specific component in a battery or other device and can have a more complex shape.

[0089] In some embodiments, the aerogel composition is manufactured to the correct size of the thermal control article or cut into the desired size of the thermal control article. Alternatively, or in addition, the thermal control article includes another sheet material to enhance mechanical integrity, heat resistance, mechanical resilience and / or other properties. Examples include but are not limited to silicone-based materials, polyvinylidene fluoride, chlorinated polyethylene, aromatic polyamide materials such as Kevlar (e.g., woven felt of aromatic polyamide fibers) and Kevlar nanofiber aerogels, such as those described in Lyu et al. ACS Nano 2019, 13, 2236-2245. The woven felt of Kevlar or other aromatic polyamide fibers can be impregnated with a shear thickening fluid, such as those described in US7,825,045, the contents of which are incorporated herein by reference.

[0090] In some cases, an envelope can be used to prevent dust, help maintain the shape of the thermal control product, facilitate its operation or installation, etc. The material forming the envelope is preferably a flame retardant and / or heat-resistant polymer material, including, for example, silicone, polyvinylidene fluoride (PVDF), polyethylene terephthalate (PET), chlorinated polyethylene and other similar polymers known to those skilled in the art. Alternatively, or in addition, the material for the envelope may include reinforcing fibers, such as aramid fibers, to provide puncture resistance. Reinforcement materials can be used in combination with other polymers, or the envelope can be formed entirely of such polymers, such as woven cloth of aramid fibers. In one embodiment, the envelope may include one or two polymer films, such as PET films, arranged around the two planar sides of the aerogel composition. In some embodiments, a frame such as silicone rubber may be arranged around the edges of the aerogel composition and the envelope to seal the envelope and facilitate the handling of the resulting thermal control product.

[0091] Alternatively, or in addition, the thermal control article may include several layers of aerogel compositions stacked on each other. Optionally, the layers may be separated by any material described above in conjunction with the envelope. Alternatively, or in addition, the layers may be separated by foam pads or mica sheets to further improve insulation performance. Alternatively, or in addition, such layers may be used on the outside of an aerogel composition layer stack (laminate). In some embodiments, it may be desirable to include a thermally conductive material configured to transfer heat to, for example, a radiator in a controlled manner. The various layers may be connected to each other, acupunctured, or encapsulated by an envelope to maintain a stacked structure by any suitable adhesive known to those skilled in the art.

[0092] Alternatively, or in addition, the thermal control article may include a coating. For example, a polymer or prepolymer solution or emulsion may be sprayed, brushed, cast or otherwise applied to one or more outer surfaces of an aerogel composition or stack and cured. Suitable cured polymers include polyolefins, silicones, polyvinyl alcohol, starch, polytetrafluoroethylene, phenolic aldehydes, melamine, phenol formaldehyde, acrylic polymers and other polymers known to those skilled in the art. Such a coating can provide functions similar to the envelope discussed above, but with less material. Alternatively, or in addition, the aerogel composition may be surface treated, for example, it may be hydrophobized. The aerogel composition may be contacted with a hydrophobizing agent such as a silane compound, a silazane compound or a disiloxane compound. Examples of silane compounds include those having the formula R' x SiX 4-x Alkyl halosilane and having formula R' x Si(OR”) 4-x Alkoxysilane, wherein R' is selected from C1-C 10 Branched and straight chain alkyl or alkenyl, C3-C 10 Cycloalkyl and C6-C 10 The aerogel composition can be immersed in the hydrophobizing agent directly or exposed to the vapor of the hydrophobizing agent. Alternatively, the aerogel composition can be immersed in a mixture of the hydrophobizing agent and a suitable solvent. The temperature and pH of the treatment medium can be adjusted as known to those skilled in the art to manipulate the degree of treatment. Exemplary treatment agents include, but are not limited to, trimethylchlorosilane, dimethyldichlorosilane, hexamethyldisilazane, hexamethyldisiloxane, and other hydrophobizing agents known to those skilled in the art. The hydrophobizing agent is preferably water-soluble and / or has a boiling point below 200°C, below 150°C, or preferably below 100°C.

[0093] The aerogel composition and / or thermal control article may have a thickness of 0.3-6 mm, such as 0.3-5 mm, 0.4-4 mm, 1-3 mm, or 1.5-2.5 mm. In some embodiments, after drying the aerogel composition, such as during assembly of the thermal control article, such as between rollers or press plates, at least a portion of the components are compressed to reduce the final thickness of the product article. Preferably, the aerogel composition and / or thermal control article is self-supporting. That is, the aerogel composition and flocculation system of aerogel, fiber, sunscreen and other particulate additives and polymer binder can be handled and manipulated without loss of cohesion. Non-self-supporting aerogel compositions may require a backing or scrim to maintain cohesion.

[0094] The aerogel composition and / or thermal control article may exhibit excellent thermal stability. For example, according to ASTM-C356, after aging at 650°C, the thermal control article may shrink by less than 2%. According to test method ASTM C518, the thermal conductivity of the aerogel composition and / or thermal control article at 25°C may be less than 30 mW / m·K, more preferably less than 25 mW / m·K, such as 5-25 mW / m·K, or 8-15 mW / m·K, or 17-30 mW / m·K, or 15-25 mW / m·K, or 20-30 mW / m·K.

[0095] The aerogel composition and / or thermal management article may have a tensile strength of 0.1-5 MPa, such as 0.1-3 MPa or 0.15-2 MPa.

[0096] The aerogel composition and / or thermal management article may be flexible, a property that may be measured according to ASTM C1101 or another suitable technique. Manual bend testing may be useful, particularly in the initial screening stages of a product.

[0097] In a specific implementation, the aerogel composition and / or thermal control article has a non-flammable flammability rating according to UL94-V0.

[0098] Alternatively, or in addition, the aerogel composition and / or thermal management article can be compressible. For example, as measured by ASTM C 165-05, it can have a compression modulus of 0.1-100 MPa at 50% compression, such as 0.1-1 MPa, 1-10 MPa, 5-30 MPa, 10-50 MPa, or 30-100 MPa.

[0099] The present invention includes the following aspects / embodiments / features in any order and / or in any combination:

[0100] 1. An aerogel composition comprising:

[0101] Aerogel particles;

[0102] A fibrous component comprising one or more materials selected from polymer fibers and inorganic fibers, wherein the weight ratio of aerogel particles:fibrous component is 1:3-10:1; and

[0103] 3 to 25% by weight of a polymer, based on the total weight of the composition,

[0104] The composition has a thickness of 0.3-6 mm, a thermal conductivity of up to 32 mW / mK at 25° C., a UL-94 rating of V0, a ​​tensile strength of 0.09-5 MPa, and a 3 density.

[0105] 2. The composition of any preceding or following embodiment / feature / aspect, wherein the aerogel particles are silica aerogel particles.

[0106] 3. The composition of any preceding or following embodiment / feature / aspect, wherein the silica aerogel particles are hydrophobic.

[0107] 4. The composition of any preceding or following embodiment / feature / aspect, wherein the composition comprises 15-65 wt % aerogel particles, for example, 20-60 wt %, 25-55 wt %, 30-50 wt %, or 35-45 wt %.

[0108] 5. The composition of any preceding or following embodiment / feature / aspect, wherein the aerogel particles have a particle size in the range of 0.1 mm-5 mm, for example, 0.1 mm-4 mm, 0.1 mm-1.5 mm, or 1 mm-4 mm.

[0109] 6. The composition of any preceding or following embodiment / feature / aspect, wherein the weight ratio of aerogel particles:fibrous component is 1:2-10:1, 1:3-3:1, 1:2-2:1, 1.2:1-9:1, 1:2-7:1, or 1:1-5:1.

[0110] 7. The composition of any preceding or following embodiment / feature / aspect, wherein the fibrous component is present in an amount of 5-55 wt%, for example, 10-50 wt%, 15-40 wt%, 20-35 wt%, or 10-30 wt%.

[0111] 8. The composition of any preceding or following embodiment / feature / aspect, wherein the fibrous component comprises glass fibers, ceramic fibers, or both.

[0112] 9. The composition of any preceding or following embodiment / feature / aspect, wherein the fibrous component comprises a blend of primary fibers and one or more secondary fibers.

[0113] 10. The composition of any preceding or following embodiment / feature / aspect, wherein the primary fiber comprises glass fiber or ceramic fiber, and the secondary fiber is selected from ceramic wool, glass fiber, ceramic fiber, aramid fiber, PBI fiber, cellulose fiber, cotton fiber, carbon fiber, acrylic fiber, polyvinyl alcohol (PVA) fiber, phenolic fiber, polyolefin fiber, and any mixture of the former.

[0114] 11. The composition of any preceding or following embodiment / feature / aspect, wherein the secondary fiber is selected from the group consisting of ceramic wool, glass fiber, ceramic fiber, aramid fiber, and PBI fiber.

[0115] 12. The composition of any preceding or following embodiment / feature / aspect, wherein the primary fibers and the secondary fibers differ in at least one of aspect ratio, length, length distribution, diameter, diameter distribution, and composition.

[0116] 13. The composition of any preceding or following embodiment / feature / aspect, wherein the primary fibers are present in the composition in a greater proportion than the secondary fibers.

[0117] 14. The composition of any preceding or following embodiment / feature / aspect, wherein the weight ratio of the primary fiber to the secondary fiber is 100:1-1:100, for example, 50:1-1:50, 35:1-1:35, 25:1-1:25, 15:1-1:15, 10:1-1:10, 7:1-1:7, 5:1-1:5, 4:1-1:4, 3:1-1:3, or 2:1-1:2.

[0118] 15. The composition of any preceding or following embodiment / feature / aspect, having a thermal conductivity of 5 mW / m·K-32 mW / m·K at 25°C, for example, 10 mW / m·K-30 mW / m·K, 17 mW / m·K-25 mW / m·K, or 15 mW / m·K-25 mW / m·K.

[0119] 16. The composition of any preceding or following embodiment / feature / aspect, further comprising a sunscreen.

[0120] 17. The composition of any preceding or following embodiment / feature / aspect, wherein the opacifier is selected from carbon black, mica, alumina, graphite, titanium dioxide, rutile sand, iron oxide, silicon carbide (SiC), graphite, zirconium dioxide, and combinations of two or more of these.

[0121] 18. The composition of any preceding or following embodiment / feature / aspect, wherein the sunscreen is present in an amount up to 10 wt%, for example, 0.5 wt%-8 wt%, 0.75 wt%-5 wt%, or 1 wt%-3 wt%.

[0122] 19. The composition of any preceding or following embodiment / feature / aspect, wherein the composition has a thickness of 0.3-6 mm, for example, 0.4-4 mm, 1-3 mm, or 1.5-2.5 mm.

[0123] 20. The composition of any preceding or following embodiment / feature / aspect, wherein the composition has a tensile strength of 0.1-3 MPa or 0.15-2 MPa.

[0124] 21. The composition of any preceding or following embodiment / feature / aspect, further comprising one or more of a flame retardant, a flame retarder, an endothermic material or a phase change material.

[0125] 22. The composition of any preceding or following embodiment / feature / aspect, having a viscosity of 0.1-0.6 g / cm 3 Density, for example, 0.15-0.5 g / cm 3 , 0.15-0.4g / cm 3 , or 0.2-0.35g / cm 3 .

[0126] 23. The composition of any preceding or following embodiment / feature / aspect, wherein the polymer comprises a surfactant, a dispersant, or both.

[0127] 24. The composition of any preceding or following embodiment / feature / aspect, wherein the surfactant or dispersant is selected from ionic (anionic and cationic) surfactants and dispersants, amphoteric surfactants and dispersants, nonionic surfactants and dispersants, and high molecular weight surfactants and dispersants.

[0128] 25. The composition of any preceding or following embodiment / feature / aspect, wherein the dispersant is a cationic dispersant, for example, having an HLB ratio of 2-20.

[0129] 26. The composition of any preceding or following embodiment / feature / aspect, wherein the cationic dispersant comprises ethylene oxide and propylene oxide oligomers having a molar ratio of ethylene oxide units to propylene oxide units of 0.1:1 to 11:1.

[0130] 27. The composition of any preceding or following embodiment / feature / aspect, wherein the polymer comprises a binder.

[0131] 28. The composition of any preceding or following embodiment / feature / aspect, wherein the adhesive is selected from silicone, polyurethane, polyvinyl alcohol, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, styrene-butadiene copolymer, and acrylate (acrylic) polymers.

[0132] 29. The composition of any preceding or following embodiment / feature / aspect, wherein the adhesive is selected from acrylic polymers, silicones, polyurethanes, and combinations of two or more of these.

[0133] 30. The composition of any preceding or following embodiment / feature / aspect, wherein the weight proportion of the polymer is 4-20%, 5-10%, 10-15%, 15-20%, 20-25%, 5%-15%, or 8%-17% based on the total weight of the composition.

[0134] 31. The composition of any preceding or following embodiment / feature / aspect, further comprising elastomeric particles.

[0135] 32. The composition of any preceding or following embodiment / feature / aspect, wherein the polymer comprises a flocculation system comprising a flocculant and a flocculation polymer.

[0136] 33. The composition of any preceding or following embodiment / feature / aspect, wherein the flocculant is polymeric.

[0137] 34. The composition of any preceding or following embodiment / feature / aspect, wherein a) the flocculant is cationic and the flocculating polymer is anionic, or b) the flocculant is anionic and the flocculating polymer is cationic.

[0138] 35. A composition of any preceding or following embodiment / feature / aspect, wherein the polymer comprises a flocculation system, the flocculation system comprising a flocculant and a flocculation polymer, an optional binder, a dispersant, and an optional defoaming agent, wherein the total amount of the flocculation system and the optional binder in the composition is 3-20 wt%, e.g., 4-16 wt%.

[0139] 36. The composition of any preceding or following embodiment / feature / aspect, wherein the composition is self-supporting.

[0140] 37. A method of making a nonwoven aerogel composition, the method comprising:

[0141] mixing aerogel particles, a fibrous component, at least one polymeric component, and an aqueous solvent to form an aqueous slurry, wherein the weight ratio of aerogel particles:fibrous component is 1:3-10:1;

[0142] flocculating and / or coagulating the aqueous slurry to form a floc comprising the aerogel particles, the fibrous component, at least a portion of the polymeric component, and a supernatant;

[0143] dewatering the flocs; and

[0144] The flocculates are dried to produce the nonwoven aerogel composition having a thickness of 0.3-6 mm, a thermal conductivity of up to 32 mW / mK at 25° C., a UL-94 rating of V0, a ​​tensile strength of 0.09-5 MPa, and a strength of 0.1-0.6 g / cm 3 The density of

[0145] The total amount of the polymeric components in the floccules and the supernatant is 3-25% based on the total amount of materials in the floccules and the supernatant except the aqueous solvent.

[0146] 38. The method of any preceding or following embodiment / feature / aspect, wherein the aqueous solvent comprises less than 5 wt % organic solvent, eg, less than 3 wt % or less than 1 wt %.

[0147] 39. The method of any preceding or following embodiment / feature / aspect, wherein the total amount of solid material including the polymeric component in the aqueous slurry is 5 wt%-25 wt%, for example, 5-10 wt%, 10-15 wt%, 15-20 wt%, or 20-25 wt%.

[0148] 40. The method of any preceding or following embodiment / feature / aspect, further comprising compressing the dewatered floc.

[0149] 41. The method of any preceding or following embodiment / feature / aspect, further comprising compressing the nonwoven aerogel blanket.

[0150] 42. The method of any preceding or following embodiment / feature / aspect, wherein the aerogel particles are silica aerogel particles.

[0151] 43. The method of any preceding or following embodiment / feature / aspect, wherein said silica aerogel particles are hydrophobic.

[0152] 44. The method of any preceding or following embodiment / feature / aspect, wherein the total amount of aerogel particles in the flocculent and the supernatant is 15-65 wt%, such as 20-60 wt%, 25-55 wt%, 30-50 wt%, or 35-45 wt%, excluding the aqueous solvent.

[0153] 45. The method of any preceding or following embodiment / feature / aspect, wherein the aerogel particles have a particle size in the range of 0.1 mm-5 mm, for example, 0.1 mm-4 mm, 0.1 mm-1.5 mm, or 1 mm-4 mm.

[0154] 46. ​​The method of any preceding or following embodiment / feature / aspect, wherein the weight ratio of aerogel particles:fibrous component is 1:2-10:1, 1:3-3:1, 1:2-2:1, 1.2:1-9:1, 1:2-7:1, or 1:1-5:1.

[0155] 47. The method of any preceding or following embodiment / feature / aspect, wherein the fibrous component is present in the floc and the supernatant in an amount of 5-55 wt%, such as 10-50 wt%, 15-40 wt%, 20-35 wt%, or 10-30 wt%, excluding the aqueous solvent.

[0156] 48. The method of any preceding or following embodiment / feature / aspect, wherein the fibrous component comprises glass fibers, ceramic fibers, or both.

[0157] 49. The method of any preceding or following embodiment / feature / aspect, wherein the fibrous component comprises a blend of primary fibers and one or more secondary fibers.

[0158] 50. The method of any preceding or following embodiment / feature / aspect, wherein the primary fiber comprises glass fiber or ceramic fiber, and the secondary fiber is selected from ceramic wool, glass fiber, ceramic fiber, aramid fiber, PBI fiber, cellulose fiber, cotton fiber, carbon fiber, acrylic fiber, polyvinyl alcohol (PVA) fiber, phenolic fiber, polyolefin fiber, and any mixture of the former.

[0159] 51. The method of any preceding or following embodiment / feature / aspect, wherein the secondary fiber is selected from the group consisting of ceramic wool, glass fiber, ceramic fiber, aramid fiber, and PBI fiber.

[0160] 52. The method of any preceding or following embodiment / feature / aspect, wherein the primary fibers and the secondary fibers differ in at least one of aspect ratio, length, length distribution, diameter, diameter distribution, and composition.

[0161] 53. The method of any preceding or following embodiment / feature / aspect, wherein the primary fibers are present in the composition in a greater proportion than the secondary fibers.

[0162] 54. The method of any preceding or following embodiment / feature / aspect, wherein the weight ratio of the primary fiber to the secondary fiber is 100:1-1:100, for example, 50:1-1:50, 35:1-1:35, 25:1-1:25, 15:1-1:15, 10:1-1:10, 7:1-1:7, 5:1-1:5, 4:1-1:4, 3:1-1:3, or 2:1-1:2.

[0163] 55. The method of any preceding or following embodiment / feature / aspect, wherein the nonwoven aerogel composition has a thermal conductivity at 25° C. of 5 mW / m·K to 32 mW / m·K, for example, 10 mW / m·K to 30 mW / m·K, 17 mW / m·K to 25 mW / m·K, or 15 mW / m·K to 25 mW / m·K.

[0164] 56. The method of any preceding or following embodiment / feature / aspect, wherein mixing further comprises including an opacifier in the aqueous slurry.

[0165] 57. The method of any preceding or following embodiment / feature / aspect, wherein the opacifier is selected from carbon black, mica, aluminum oxide, graphite, titanium dioxide, rutile sand, iron oxide, silicon carbide (SiC), graphite, zirconium dioxide, and combinations of two or more of these.

[0166] 58. The method of any preceding or following embodiment / feature / aspect, wherein the sunscreen is present in the flocculent and supernatant in an amount up to 10 wt %, e.g., 0.5 wt %-8 wt %, 0.75 wt %-5 wt %, or 1 wt %-3 wt %, excluding the aqueous solvent.

[0167] 59. The method of any preceding or following embodiment / feature / aspect, wherein the nonwoven aerogel composition has a thickness of 0.3-6 mm, eg, 0.4-4 mm, 1-3 mm, or 1.5-2.5 mm.

[0168] 60. The method of any preceding or following embodiment / feature / aspect, wherein the nonwoven aerogel composition has a tensile strength of 0.1-3 MPa or 0.15-2 MPa.

[0169] 61. The method of any preceding or following embodiment / feature / aspect, wherein mixing further comprises including one or more of a flame retardant, a flame retarder, an endothermic material, or a phase change material in the aqueous slurry.

[0170] 62. The method of any preceding or following embodiment / feature / aspect, wherein the nonwoven aerogel composition has a thickness of 0.1-0.6 g / cm 3 Density, for example, 0.15-0.5 g / cm 3 , 0.15-0.4g / cm 3 , or 0.2-0.35g / cm 3 .

[0171] 63. The method of any preceding or following embodiment / feature / aspect, wherein the polymeric component comprises a surfactant, a dispersant, or both.

[0172] 64. The method of any preceding or following embodiment / feature / aspect, wherein the surfactant or dispersant is selected from ionic (anionic and cationic) surfactants and dispersants, amphoteric surfactants and dispersants, nonionic surfactants and dispersants, and high molecular weight surfactants and dispersants.

[0173] 65. The method of any preceding or following embodiment / feature / aspect, wherein the dispersant is a cationic dispersant, for example, having an HLB ratio of 2-20.

[0174] 66. The method of any preceding or following embodiment / feature / aspect, wherein the cationic dispersant comprises ethylene oxide and propylene oxide oligomers having a molar ratio of ethylene oxide units to propylene oxide units of 0.1:1 to 11:1.

[0175] 67. The method of any preceding or following embodiment / feature / aspect, wherein the polymeric component further comprises a defoaming agent.

[0176] 68. The method of any preceding or following embodiment / feature / aspect, wherein the polymeric component comprises a binder.

[0177] 69. The method of any preceding or following embodiment / feature / aspect, wherein the adhesive is selected from silicone, polyurethane, polyvinyl alcohol, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, styrene-butadiene copolymer, and acrylate (acrylic) polymers.

[0178] 70. The method of any preceding or following embodiment / feature / aspect, wherein the adhesive is selected from the group consisting of acrylic polymers, silicones, polyurethanes, and combinations of two or more of these.

[0179] 71. The method of any preceding or following embodiment / feature / aspect, wherein the weight ratio of the polymeric components in the flocculent and the supernatant is 4-20%, 5-10%, 10-15%, 15-20%, 20-25%, 5%-15%, or 8%-17%, excluding the aqueous solvent.

[0180] 72. The method of any preceding or following embodiment / feature / aspect, wherein mixing further comprises including elastomeric particles in the aqueous slurry.

[0181] 73. The method of any preceding or following embodiment / feature / aspect, wherein one or more of flocculation or coagulation comprises adding a flocculant to the aqueous slurry.

[0182] 74. The method of any preceding or following embodiment / feature / aspect, wherein the flocculant is polymeric.

[0183] 75. The method of any preceding or following embodiment / feature / aspect, wherein the polymeric component comprises a flocculating polymer, and wherein a) the flocculant is cationic and the flocculating polymer is anionic or b) the flocculant is anionic and the flocculating polymer is cationic.

[0184] 76. The method of any preceding or following embodiment / feature / aspect, wherein the total amount of flocculant, flocculating polymer and optional binder in the floc and supernatant is 3-20 wt%, such as 4-16 wt%, excluding the aqueous solvent.

[0185] 77. The method of any preceding or following embodiment / feature / aspect 6, wherein the nonwoven aerogel composition is self-supporting.

[0186] 78. The method of any preceding or following embodiment / feature / aspect, further comprising coating a polymer or oligomer solution or emulsion on the dried aerogel composition and curing the solution or emulsion to form a coating on the aerogel composition.

[0187] 79. The method of any preceding or following embodiment / feature / aspect, wherein the coating comprises polyolefins, silicone polymers, polyvinyl alcohol, starch, polytetrafluoroethylene, phenolic polymers, melamine polymers, phenol formaldehyde, and acrylic polymers.

[0188] 80. The method of any preceding or following embodiment / feature / aspect, further comprising treating the aerogel composition with a hydrophobic agent.

[0189] 81. The method of any preceding or following embodiment / feature / aspect, wherein the hydrophobic agent is selected from a silane compound, a silazane compound, or a disiloxane compound.

[0190] 82. The method of any preceding or following embodiment / feature / aspect, wherein the hydrophobic agent is selected from trimethylchlorosilane, dimethyldichlorosilane, hexamethyldisilazane and hexamethyldisiloxane.

[0191] 83. An aerogel composition prepared by the method of any preceding or following embodiment / feature / aspect.

[0192] 84. A thermal control article comprising the aerogel composition of any preceding or following embodiment / feature / aspect.

[0193] 85. The thermal control article of any preceding or following embodiment / feature / aspect, wherein the article is a blanket, a sheet, a felt, or a mat.

[0194] 86. The thermal management article according to any preceding or following embodiment / feature / aspect, wherein the article is a flexible nonwoven blanket.

[0195] 87. The thermal control article of any preceding or following embodiment / feature / aspect, having a non-flammable flammability rating according to UL94-V0.

[0196] 88. The thermal control article according to any preceding or following embodiment / feature / aspect, having a thermal conductivity at 25°C of up to 30 mW / mK.

[0197] 89. The thermal control article according to any preceding or following embodiment / feature / aspect, having a thermal conductivity at 25°C of 5mW / m·K-30mW / m·K, for example, 17mW / m·K-30mW / m·K or 15mW / m·K-25mW / m·K.

[0198] 90. The thermal control article according to any preceding or following embodiment / feature / aspect, having a tensile strength of 0.09-5 MPa, for example, 0.1-3 MPa or 0.15-2 MPa.

[0199] 91. The thermal control article according to any preceding or following embodiment / feature / aspect, comprising a plurality of stacked layers of the aerogel composition.

[0200] 92. The thermal control article according to any preceding or following embodiment / feature / aspect, further comprising one or more layers independently comprising woven polymer felt, foam pad, mica sheet, or thermally conductive material.

[0201] 93. The thermal control article according to any preceding or following embodiment / feature / aspect, wherein at least one surface of the thermal control article is covered by a polymer film.

[0202] 94. The thermal control article according to any preceding or following embodiment / feature / aspect, wherein the polymer is selected from silicone polymers, polyvinylidene fluoride, polyethylene terephthalate, and chlorinated polyethylene.

[0203] 95. The thermal control article according to any preceding or following embodiment / feature / aspect, wherein the polymer film comprises reinforcing fibers.

[0204] 96. The thermal control article according to any preceding or following embodiment / feature / aspect, further comprising a coating.

[0205] 97. A thermal control article according to any preceding or following embodiment / feature / aspect, wherein the coating comprises polyolefins, silicone polymers, polyvinyl alcohol, starch, polytetrafluoroethylene, phenolic polymers, melamine polymers, phenol formaldehyde, and acrylic polymers.

[0206] 98. An electric vehicle comprising a thermal control article according to any preceding or following embodiment / feature / aspect.

[0207] 99. A battery comprising the thermal management article according to any preceding or following embodiment / feature / aspect.

[0208] The invention is further illustrated in the following non-limiting Examples section.

[0209] Example

[0210] Examples 1-8 and Comparative Examples 1 and 2

[0211] Nonwoven blankets containing aerogel particles (except Comparative Example 1) and combinations of different particles (Table 1) were produced in a wet-laid process as described below. Dispersant (Barlox 12 (30 wt. % lauryl dimethylamine oxide in dispersion) or Jeffamine M2070, denoted as B or J in Table 1 below), Nalclear 7768 polymer (Nalco) and Foamkill were blended in a WARING benchtop heavy duty blender according to the formulation in Table 1. TM 830F defoamer (Crucible Chemical) was dispersed in water to form white water (process water) and mixed under high shear for 10 seconds to form process water. 7001C5 ceramic fiber (Unifrax), 1 / 4" E-06 chopped glass fiber (Lauscha Fiber International), P200 aerogel particles (Cabot Corporation) (Examples 1-7) or a mixture of P200 aerogel (84%) and silicon carbide (16%) (Comparative Example 2), 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services) and aluminum trihydroxide (ATH, Sigma Aldrich) were added to a WARING heavy duty blender in the amounts listed in Table 1. The blend in the blender was mixed under high shear (2000 rpm) for 20 seconds to form a solid dispersion. Novacryl PSR 300 and Dow HV 496 resin was added to the blender and mixed under high shear for another 20 seconds to prepare a slurry, which was then transferred to a 5L beaker. To destabilize the slurry system, polydiallyldimethylammonium chloride (PDADMAC, 60-80 cps viscosity, 20 wt% polymer in the dispersion) or Superfloc 577 flocculant (50% polymer in the dispersion, Kemira) from SigmaAldrich was added to the slurry to produce flocs. Typically, 2-3 grams of flocculant was added to the dispersion until a dense flocculant layer formed on the top. After flocculation, the slurry was passed through a single-layer wet-lay forming wire. The flocculation was retained by the forming wire and evenly distributed throughout it. The forming wire was then passed over a vacuum to remove additional water from the aerogel flocculation. As shown in Table 1, some samples were passed through a roller press to squeeze out some of the water and pack the various components more compactly. All blankets were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes.

[0212] Example 8 was produced by a wet-laid process as follows: 1 liter of water was mixed with a dispersant, Nalclear 7768 polymer (30 wt% polymer emulsion, Nalco), Foamkill TM 830F defoamer was mixed in a WARING benchtop heavy duty blender in the amounts shown in Table 1 and mixed under high shear for 10 seconds. This water was combined with 12 L of water in a 5 gallon bucket to form process water. 1 L of process water was mixed with P200 aerogel, 7001C5 ceramic fiber, 44 micron rutile titanium dioxide sand, F600 silicon carbide and aluminum trihydroxide are scooped back into the WARING blender together. The mixture in the blender is mixed under high shear for 20 seconds to form a solid dispersion. As shown in Table 1, Novacryl PSR 300 and Dow HV 496 resins are added to the blender, and mixed under high shear for another 20 seconds to prepare a slurry, which is then transferred to a 5-gallon bucket. The slurry in the bucket is mixed with a paddle until uniform, and then PDADMAC is added dropwise under constant mixing in the amount shown in Table 1 to flocculate the system. The slurry is then poured into a 12x12 headbox, where the forming net is suspended above a complete 20L well. The material is mixed in the headbox to evenly redistribute the flocs, and the flocs are floated to the surface to confirm the uniformity of the layer before the valve is opened, all water is dripped from the headbox and the flocs are retained on the forming net. The forming wire was then passed over a vacuum to remove additional water from the aerogel floes. The sample was rolled to squeeze out some of the water and pack the various components more tightly before being removed from the forming wire and dried at 170°C for about 20 minutes.

[0213] The sample thickness was measured with a thickness gauge. Thermal conductivity was measured at room temperature and 140°C using a LaserComp heat flow meter instrument according to ASTM C518; the standard deviation represents the standard deviation of the average of two readings during the measurement. The blanket of Comparative Example 1 was too thin for thermal conductivity measurements, so a polycarbonate (PC) pad was used to support the material during testing. The thermal conductivity (TC) was calculated by measuring the following data: The TC of the 11.55 mm thick PC pad alone was 196.69 mW / mK. The TC of the 12.62 mm thick PC pad and ceramic sample was 156.67 mW / mK. The TC of the ceramic sample (1.11 mm thick) was calculated using the following equation: 1.11 / TCCeramic+11.55 / TC PC =12.62 / TC (ceramic + PC). Compression modulus was measured according to ASTM C165, repeated three times. Flammability was measured according to UL94 standard. Tensile strength (maximum load) was measured according to ASTM D5035, repeated three times. The total amount of polymeric substances in Examples 1-3 was 12% by weight, and 21% by weight for Examples 4-7. The total amount of polymeric substances in Example 8 was 17%. The total amount of polymeric substances in Comparative Example 2 was 26% by weight. Excluding dispersants and defoamers, the total amount of polymeric substances in Examples 1-3 and 8 was 7% by weight, and 12% by weight in Examples 4-7. Excluding dispersants and defoamers, the total amount of polymeric substances in Comparative Example 2 was 22%.

[0214] Table 1. Wet-laid nonwoven blankets containing aerogel particles

[0215]

[0216]

[0217] *A mixture of 84% P200 aerogel (Cabot Corporation) and 16% silicon carbide.

[0218] Example 9

[0219] Experiments were conducted to evaluate the properties and / or performance of several nonwoven blankets. Nonwoven blankets having only one type of fiber ( For Examples 9-2 to 9-7, the composition further comprises an additional (secondary) fibrous component. For example, Example 9-3 uses chopped glass fibers (6 mm E-glass chopped fibers with a diameter of 6 μm, from Lauscha Fiber International), while the secondary fibers in Example 9-5 are 100 silica gel fiber (Textile Technologies Europe Ltd.).

[0220] Other blankets were prepared according to the embodiments described herein. Specifically, Examples 9-2 and 9-7 used PBI fibers (0.25 inch long (6.35 mm), about 1.1 micron diameter, from PBI Performance Products, Inc.) at relatively low and relatively high loads, respectively. Aramid fibers (12 mm aramid fibers, 12 micron diameter, from Endnus New Material (Donguan) Co., Ltd) were used in Example 9-3, and ceramic wool (ceramic fiber block, high purity, 2300 ° F) was used in Example 9-6, from Ceramaterials LLC). The materials and amounts used to prepare the blankets are shown in Table 2 below.

[0221] Table 2

[0222] 9-1 9-2 9-3 9-4 9-5 9-6 9-7 Components Dosage(g) P200 Aerogel 16.07 16.07 16.07 16.07 16.07 16.07 16.06 Ceramic Fiber 9.64 9.64 9.64 9.64 9.64 9.64 8.03 PBI Fiber 0 1.93 0 0 0 0 8.03 Chopped Glass 0 0 1.93 0 0 0 0 Aramid fiber 0 0 0 1.93 0 0 0 Silicone fiber 0 0 0 0 1.93 0 0 Ceramic wool 0 0 0 0 0 1.93 0 rutile sand 2.33 2.33 2.33 2.33 2.33 2.33 2.91 Silicon Carbide 2.33 2.33 2.33 2.33 2.33 2.33 2.91 Aluminum trihydroxide 0.74 0.74 0.74 0.74 0.74 0.74 0.93 Surfactants 2.97 2.97 2.97 2.97 2.97 2.97 3.71 Nalclear Polymers 3.34 3.34 3.34 3.34 3.34 3.34 4.18 Defoaming agent 2.97 2.97 2.97 2.97 2.97 2.97 3.71 Acrylic adhesive 0.42 0.42 0.42 0.42 0.42 0.42 0.52 Silicone Adhesives 8.14 8.14 8.14 8.14 8.14 8.14 8.14 Flocculants 4.87 4.85 4.9 5.01 4.89 4.89 5.05

[0223] The mat was produced in a wet-laid process according to the following procedure.

[0224] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (Nalco) and Foamkill were blended according to the formulation in Table 2. TM830 Defoamer (Crucible Chemical) was dispersed in water to form one (1) liter of white (process) aqueous concentrate. Mixing was performed under high shear for 10 seconds to form process water. The concentrate was then diluted in approximately 10 liters of water in a 5 gallon jug. After mixing, approximately 2 liters of the diluted process water was transferred to the Waring blender. Ceramic fiber ( 7001C5 ceramic fiber, Unifrax, a high purity coarse chopped product with an average fiber diameter of 1.5 to 2.5 microns and a fiber index of 45-55% as measured by conical elutriation), secondary fibrous material (for Examples 9-2 to 9-7), P200 aerogel particles (Cabot Corporation), 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services) and aluminum trihydroxide (ATH, Sigma Aldrich) were added to a WARING heavy duty blender in the amounts listed in Table 1. The mixture in the blender was mixed under high shear (15000 rpm) for 20 seconds to form a paste dispersion. Acrylic binder (Novacryl PSR 300, 60 wt% polymer in dispersion, Synthomer) and silicone binder (Dowsil HV 496 resin, Dow) were added to the blender and mixed under high shear for an additional 20 seconds to prepare a slurry which was added to the remaining process water in the 5 gallon tank. In addition to the amounts shown in the table below, a small amount (up to 0.4-0.5 g) of Foamkill TM 830 defoamer was stirred into the system to account for additional foam generation. To destabilize the slurry system, a flocculant (polydiallyl dimethyl ammonium chloride (PDADMAC), 60-80 cps viscosity, 20 wt% polymer in the dispersion, from Sigma Aldrich) was added to the slurry to produce flocs. Typically, 4-5 grams of flocculant were added to the dispersion (as shown in Table 2) until a dense flocculant layer formed on the top. The total amount of polymer was 21-22% relative to the particulate and polymer components.

[0225] After flocculation, the slurry was discharged through a single layer of wet-laid forming wire to produce a 30 cm x 30 cm blanket sheet. The blanket and forming wire were then passed over a vacuum to remove additional water from the aerogel floes. The sample was passed through a roller press to squeeze out some of the water and compress the various components into a more compact form. All blankets were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes. After drying, the blanket was calendered through a double roll mill to form a thin blanket.

[0226] The blanket was evaluated for several properties. Thermal conductivity was measured using a LaserComp heat flow meter instrument according to ASTM C518. In cases where the samples were too thin to measure, they were supported on a shim and the thermal conductivity of the resulting structure (shim + blanket) was measured. The thermal conductivity of this structure was compared to the thermal conductivity measured for the shim alone to obtain the thermal conductivity of the blanket itself.

[0227] Initial flexibility evaluation was performed by manual bending, while tensile strength (maximum load) was measured according to ASTM D5035.

[0228] The results are shown in Table 3:

[0229] Table 3

[0230] Run Blanket thickness (mm) TC, RT, mW / m·K Tensile strength(MPa) Flexibility 9-1(No secondary fiber) 1.05 22.79 0.1 no 9-2 (PBI low load) 1.15 24.90 0.5 yes 9-3(Cut glass) 0.98 23.86 0.3 no 9-4(aramid) 1.02 24.12 0.2 yes 9-5(Silica gel fiber) 0.98 23.08 0.2 no 9-6(Ceramic cotton) 0.94 23.61 0.4 no 9-7 (PBI high load) 2.1 25.64 0.5 yes

[0231] As shown in Table 2, the PBI minor fibers appear to contribute to the tensile strength of the blanket, with greater effects observed at higher loads.

[0232] The ceramic wool blanket exhibited comparable tensile strength to the blanket without the minor fibers; however, its thermal conductivity compared very well to that of Blanket 1.

[0233] Although Carpet 1 was not found to be flexible (under the manual bend test), the polymeric fibrous component appeared to increase the flexibility of the carpet product.

[0234] All blankets had acceptable thermal conductivity and had a V0 rating using the UL94 flammability test.

[0235] Example 10

[0236] Experiments were conducted to evaluate the properties and / or performance of several nonwoven blankets. Ceramic Fibers ( 7001C5 ceramic fiber) was used in combination with 6 mm chopped E-glass (Yiquedok) (Examples 10-1, 10-2), 12 mm glass fiber (Vetrotex EC-6-12-SP fiber from Saint-Gobain, Examples 10-3, 10-4) or glass microfiber (microfiber B-06-F from Lauscha Fiber International, 0.65 micron diameter, Example 10-5) in the amounts listed in Table 4.

[0237] The mat was produced in a wet-laid process according to the following procedure.

[0238] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (25% polymer in the dispersion, Nalco) and Foamkill TM 830 defoamer (30% polymer in dispersion, Crucible Chemical) was dispersed in water to form one (1) liter of white (process) aqueous concentrate. Mixing was performed under high shear for 10 seconds to form process water. The concentrate was then diluted to about 3 liters of water. After mixing, about 1.5 liters of the diluted process water were transferred to a Waring blender. For Examples 10-1, 10-4, and 10-5, glass fiber, ENTERA EV5200 aerogel particles (0.1-1.2 mm diameter, Cabot Corporation), 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services), and aluminum trihydroxide (ATH, ThermoFisher Scientific) were added to a WARING heavy duty blender in the amounts listed in Table 4. The mixture in the blender was mixed under high shear (15000 rpm) for 40 seconds. For Examples 10-2 and 10-3, glass fibers were added and mixed for 40 seconds, followed by aerogel, titanium dioxide, and ATH, wherein the granules were blended for another 40 seconds. For all Examples, ceramic fibers, polyurethane binder (Joncryl FLX 5201 polyurethane from BASF, 30% polymer in dispersion) and silicone binder (Dowsil HV 496 resin, 40% polymer in dispersion, Dow) were added to the blender and mixed for another 20 seconds under high shear to prepare a slurry, which was added to the remaining process water. To destabilize the slurry system, 2.25-2.75 g of flocculant (polydiallyl dimethyl ammonium chloride (PDADMAC), 60-80 cps viscosity, 20 wt% polymer in dispersion, from Sigma Aldrich) was added to the slurry to produce flocs.

[0239] After flocculation, the slurry was discharged through a single-layer wet-laid forming wire to produce a 30 cm×30 cm mat. The mat and forming wire were then passed over a vacuum to remove additional water from the aerogel flocs. The samples were compressed to a thickness of about 2 mm with a heavy roller to squeeze out some water and flatten the mat to a consistent surface. All the mats were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes and then analyzed for room temperature thermal conductivity as described above; the thermal conductivity of all samples at 25°C was 23-25 ​​mW / mK. After drying, the mat was pressed between two press plates to form a thin mat 1-1.2 mm thick and then evaluated for tensile strength as described above. The total polymer loading was about 21% by weight and 11% by weight of the total solids in the slurry, excluding dispersants and defoamers. The density of all the mats after compression was 0.28 to 0.32 g / cm 3 The resulting aerogel composition is expected to meet the standards of UL94-V0 rating.

[0240] Table 4

[0241] Components (in grams) 10-1 10-2 10-3 10-4 10-5 Aerogel 9.54 9.54 9.54 9.54 9.54 Ceramic Fiber 4.57 5.71 5.71 5.71 5.71 Fiberglass 2.28 1.14 1.14 1.14 1.14 rutile sand 1.38 1.38 1.38 1.38 1.38 Silicon Carbide 1.38 1.38 1.38 1.38 1.38 ATH 0.44 0.44 0.44 0.44 0.44 Surfactants 1.76 1.76 1.76 1.76 1.76 Nalclear Polymers 1.984 1.984 1.984 1.984 1.984 Foamkill 1.76 1.76 1.76 1.76 1.76 PU adhesive 0.50 0.50 0.50 0.50 0.50 Silicone Adhesives 3.86 3.86 3.86 3.86 3.86 Tensile strength(MPa) 0.4 0.4 0.7 0.7 0.5

[0242] Embodiment 11

[0243] Experiments were conducted to evaluate the properties and / or performance of several nonwoven blankets. Ceramic Fibers ( 7001 C5 ceramic fiber) was used in combination with 6 mm chopped E-glass (6 micron diameter, Valmiera Glass) in the amounts listed in Table 5.

[0244] The mat was produced in a wet-laid process according to the following procedure.

[0245] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (Nalco) and Foamkill were mixed according to the formulation in Table 5. TM830 defoamer (Crucible Chemical) was dispersed in water to form one (1) liter of white (process) aqueous concentrate. Mixing was performed under high shear for 10 seconds to form process water. The concentrate was then diluted to about 3 liters of water. After mixing, about 1.5 liters of the diluted process water were transferred to the Waring blender. Glass fiber, ENTERA EV5200 aerogel particles (Cabot Corporation), 1-1.5 micron (D50) rutile titanium dioxide (Fisher Scientific), F600 silicon carbide (Sturbridge Metallurgical Services) and aluminum trihydroxide (ATH, Thermo Fisher Scientific) were added to the WARING heavy duty blender in the amounts listed in Table 5. The mixture in the blender was mixed under high shear (15000 rpm) for 40 seconds (for Examples 11-1 and 11-2) and 80 seconds (for Example 11-3). For all examples, ceramic fibers, polyurethane binder (Joncryl FLX 5201 polyurethane from BASF) and silicone binder (Dowsil HV 496 resin, Dow) were added to the blender and mixed under high shear for another 20 seconds to prepare a slurry, which was added to the remaining process water. To destabilize the slurry system, a flocculant (polydiallyl dimethyl ammonium chloride (PDADMAC), 60-80 cps viscosity, 20 wt% solids, from Sigma Aldrich) was added to the slurry in the amounts shown in Table 5 to produce flocs.

[0246] After flocculation, the slurry was discharged through a single layer of wet-laid forming wire to produce a 30 cm x 30 cm blanket. The blanket and forming wire were then passed over a vacuum to remove additional water from the aerogel flocculate. The sample was compressed to a thickness of about 2 mm with a heavy roller to squeeze out some water and flatten the blanket to a consistent surface. All blankets were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes and then analyzed for room temperature thermal conductivity as described above. After drying, the blanket was pressed between two press plates to form a thin blanket 1-1.2 mm thick and then evaluated for tensile strength as described above. The total polymer loading was 21-22 wt% and 11-12 wt% of the total solids in the slurry, excluding dispersants and defoamers. The resulting aerogel composition is expected to meet the standards of UL94-V0 rating.

[0247] Table 5

[0248] Components (in grams) 11-1 11-2 11-3 Aerogel 9.54 9.54 9.54 Ceramic Fiber 5.71 0 0 Fiberglass 1.14 4.77 4.77 rutile sand 2.07 1.38 1.38 Silicon Carbide 0 1.38 1.38 ATH 0.44 0.44 0.44 Surfactants 1.76 1.76 1.76 Nalclear Polymers 1.94 1.94 1.94 Foamkill 1.76 1.76 1.76 PU adhesive 0.50 0.50 0.50 Silicone Adhesives 3.86 3.86 3.86 Flocculants 2.32 2.29 2.11 Thermal conductivity at 25°C (mW / mK) 24.1 23.8 23.2 Tensile strength(MPa) 0.7 1.1 0.7

[0249] Example 12

[0250] Experiments were conducted to evaluate the properties and / or performance of several nonwoven blankets. Ceramic Fibers ( 7001C5 ceramic fiber) was used in combination with 12 mm glass fiber (Vetrotex EC-6-12-SP glass fiber from Saint Gobain) in the amounts listed in Table 6.

[0251] The mat was produced in a wet-laid process according to the following procedure.

[0252] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (Nalco) and Foamkill were blended according to the formulation in Table 6. TM 830 defoamer (Crucible Chemical) was dispersed in water to form one (1) liter of white (process) aqueous concentrate. Mixing was performed under high shear for 10 seconds to form process water. The concentrate was then diluted to about 3 liters of water. After mixing, about 1.5 liters of the diluted process water were transferred to the Waring blender. Glass fiber was added to the WARING heavy duty blender in the amounts listed in Table 6. The mixture in the blender was mixed under high shear (15000 rpm) for 40 seconds (for Examples 12-1 and 12-2) and 60 seconds (for Example 12-3). For all examples, ENTERA EV5200 aerogel particles (Cabot Corporation), 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services) and aluminum trihydroxide (ATH, Thermo Fisher Scientific) were added to the WARING heavy duty blender in the amounts listed in Table 6, and the mixture was blended under high shear for 40 seconds. Ceramic fiber, polyurethane binder (Joncryl FLX 5201 polyurethane from BASF) and silicone binder (Dowsil HV 496 resin, Dow) were added to the blender and mixed under high shear for another 20 seconds to prepare a slurry, which was added to the remaining process water. To destabilize the slurry system, a flocculant (polydiallyl dimethyl ammonium chloride (PDADMAC), 60-80 cps viscosity, 20 wt% solids, from Sigma Aldrich) was added to the slurry in the amounts shown in Table 6 to produce flocs.

[0253] After flocculation, the slurry was discharged through a single layer of wet-laid forming wire to produce a 30 cm x 30 cm blanket. The blanket and forming wire were then passed over a vacuum to remove additional water from the aerogel floes. The samples were compressed to a thickness of about 2 mm with a heavy roller to squeeze out some of the water and flatten the blanket to a consistent surface. All blankets were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes and then analyzed for room temperature thermal conductivity as described above; the thermal conductivity of all samples at 25°C was 23-25 ​​mW / mK. After drying, the blanket was pressed between two press plates to form a thin blanket 1-1.2 mm thick and then evaluated for tensile strength as described above. The total polymer loading was about 21% by weight and 11% by weight of the total solids in the slurry, excluding dispersants and defoamers. The density of all blankets after compression was 0.31-0.32 g / cm 3 The resulting aerogel composition is expected to meet the standards of UL94-V0 rating.

[0254] Table 6

[0255] Components (in grams) 12-1 12-2 12-3 Aerogel 9.54 9.54 9.54 Ceramic Fiber 5.71 5.71 5.14 Fiberglass 1.14 1.14 1.71 rutile sand 1.38 1.38 1.38 Silicon Carbide 1.38 1.38 1.38 ATH 0.44 0.44 0.44 Surfactants 1.76 1.76 1.76 Nalclear Polymers 1.94 1.94 1.94 Foamkill 1.76 1.76 1.76 PU adhesive 0.50 0.50 0.50 Silicone Adhesives 3.86 3.86 3.86 Flocculants 2.55 2.56 2.62 Tensile strength(MPa) 1.0 0.9 0.9

[0256] Embodiment 13

[0257] Experiments were conducted to evaluate the properties and / or performance of several nonwoven blankets. Ceramic fibers ( 7001C5 ceramic fiber) was used in combination with 12 mm glass fiber (Vetrotex EC-6-12-SP glass fiber, from Saint Gobain) and aramid fiber (12 mm aramid fiber, 12 micron diameter, from Endnus New Material (Donguan) Co., Ltd) in the amounts listed in Table 7.

[0258] The mat was produced in a wet-laid process according to the following procedure.

[0259] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (Nalco) and Foamkill were blended according to the formulation in Table 6. TM830 defoamer (Crucible Chemical) was dispersed in water to form one (1) liter of white (process) aqueous concentrate. Mixing was performed under high shear for 10 seconds to form process water. The concentrate was then diluted to about 3 liters of water. After mixing, about 1.5 liters of diluted process water were transferred to the Waring blender. Glass fiber was added to the WARING heavy duty blender in the amounts listed in Table 7. The mixture in the blender was mixed under high shear (15000 rpm) for 40 seconds. ENTERA EV5200 aerogel particles (Cabot Corporation), 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services), aluminum trihydroxide (ATH, Thermo Fisher Scientific) and aramid fiber were added to the WARING heavy duty blender in the amounts listed in Table 7, and the mixture was blended under high shear for 40 seconds. Ceramic fiber, polyurethane binder (Joncryl FLX 5201 polyurethane from BASF) and silicone binder (Dowsil HV 496 resin, Dow) were added to the blender and mixed under high shear for another 20 seconds to prepare a slurry, which was added to the remaining process water. To destabilize the slurry system, a flocculant (polydiallyl dimethyl ammonium chloride (PDADMAC), 60-80 cps viscosity, 20 wt% solids, from Sigma Aldrich) was added to the slurry in the amounts shown in Table 7 to produce flocs.

[0260] After flocculation, the slurry was discharged through a single layer of wet-laid forming wire to produce a 30 cm x 30 cm blanket. The blanket and forming wire were then passed over a vacuum to remove additional water from the aerogel flocs. The sample was compressed to a thickness of about 2 mm with a heavy roller to squeeze out some of the water and flatten the blanket to a consistent surface. All blankets were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes and then analyzed for room temperature thermal conductivity and tensile strength as described above. The total polymer loading was about 14 wt % and 4 wt % of the total solids in the slurry, excluding dispersants and defoamers. The density of Example 13-1 was 0.22 g / cm 3 The resulting aerogel composition is expected to meet the standards of UL94-V0 rating.

[0261] Table 7

[0262] Components (in grams) 13-1 13-2 Aerogel 11.92 11.92 Ceramic Fiber 6.43 7.14 Fiberglass 1.43 1.43 Aramid fiber 0.71 0 rutile sand 1.73 1.73 Silicon Carbide 1.73 1.73 ATH 0.55 0.55 Surfactants 2.2 2.2 Nalclear Polymers 2.48 2.48 Foamkill 2.2 2.2 PU adhesive 0 0 Silicone Adhesives 0 0 Flocculants 2.84 2.98 Tensile strength(MPa) 1.6 1.4 Thermal conductivity at 25°C (mW / mK) 22 to 25 22.0

[0263] Embodiment 14

[0264] Experiments were conducted to evaluate the properties and / or performance of several nonwoven blankets. Ceramic Fibers ( 7001C5 ceramic fiber) was used in combination with one or more of 3 mm chopped E glass (Vetrotex EC-6-3-SP glass fiber from Saint Gobain) (Examples 14-1, 14-2), 6 mm chopped E glass (6 micron diameter, Valmiera Glass, Example 14-4), 6 mm 6 μm diameter E glass chopped fiber (from Lauscha Fiber International), silica gel fiber (6 mm long, 8 micron diameter, Belcotex; Example 14-3), ground glass fiber (1 / 32" (0.79 mm), Fiber Glast), 3 mm aramid fiber (Donguang Sovetl Special Rope and Webbing Co.) and aramid pulp (Donguang Sovetl Special Rope and Webbing Co.) in the amounts listed in Table 8.

[0265] The mat was produced in a wet-laid process according to the following procedure.

[0266] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (Nalco) and Foamkill TM830 defoamer (Crucible Chemical) was dispersed in water to form one (1) liter of white (process) aqueous concentrate. Mixing was performed under high shear for 10 seconds to form process water. The concentrate was then diluted to about 3 liters of water. After mixing, about 1.5 liters of the diluted process water were transferred to the Waring blender. The mixing order of the remaining components is listed in Table 8; all mixing was performed under high shear (15000 rpm). Examples 14-1 and 14-2 used IC3110 aerogel (0.1-0.7 mm diameter, Cabot Corporation). Examples 14-3 and 14-4 used ENTERAEV5200 aerogel from Cabot Corporation. For all examples, 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services) and aluminum trihydroxide (ATH, Thermo Fisher Scientific) were used, while the polymer binders were a polyurethane binder (Joncryl FLX 5201 polyurethane from BASF) and a silicone binder (Dowsil HV 496 resin, Dow). After mixing, the resulting slurry was added to the remaining process water. In order to destabilize the slurry system, a flocculant (Examples 14-1, 14-3, 14-4: polydiallyl dimethyl ammonium chloride (PDADMAC, 60-80 cps viscosity, 20 wt% solids, from Sigma Aldrich); Example 14-2: Superfloc 581 flocculant, 50 wt% polymer emulsion from Kemira) was added to the slurry in the amounts shown in Table 8 to produce flocs. In Example 14-2, the as-received flocculant was diluted 1:1 with deionized water (ie, to 25% total solids loading).

[0267] After flocculation, the slurry was discharged through a single layer of wet-laid forming wire to produce a 30 cm x 30 cm blanket. The blanket and forming wire were then passed over a vacuum to remove additional water from the aerogel floes. The sample was compressed to a thickness of about 2 mm with a heavy roller to squeeze out some water and flatten the blanket to a consistent surface. All blankets were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes and then analyzed for room temperature thermal conductivity as described above. After drying, the blanket was compressed between two press plates to form a thin blanket 1-1.2 mm thick and then evaluated for tensile strength as described above. The total polymer loading was 22-24 wt% and 14-16 wt% of the total solids in the slurry, excluding dispersants and defoamers. The resulting aerogel composition is expected to meet the standards of UL94-V0 rating.

[0268] Table 8

[0269]

[0270] Embodiment 15

[0271] Experiments were conducted to evaluate the properties and / or performance of several nonwoven blankets. Ceramic fibers ( 7001C5 ceramic fibers) were used in combination with 6 mm E-glass chopped fibers having a diameter of 6 μm from Lauscha Fiber International in the amounts listed in Table 9.

[0272] The mat was produced in a wet-laid process according to the following procedure.

[0273] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (Nalco) and Foamkill were blended according to the formulation in Table 9. TM 830 defoamer (Crucible Chemical) was dispersed in water to form one (1) liter of white (process) aqueous concentrate. Mixing was performed under high shear for 10 seconds to form process water. The concentrate was then diluted to about 3 liters of water. After mixing, about 1.5 liters of diluted process water were transferred to the Waring blender. Glass fiber, ENTERA EV5200 aerogel particles (Cabot Corporation), 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services) and aluminum trihydroxide (ATH, Thermo Fisher Scientific) were added to the WARING heavy duty blender in the amounts listed in Table 9. The mixture in the blender was mixed under high shear (15000 rpm) for 40 seconds. Ceramic fiber, polyurethane binder (Joncryl FLX 5201 polyurethane from BASF) and silicone binder (Dowsil HV 496 resin, Dow) were added to the blender and mixed under high shear for another 20 seconds to prepare a slurry, which was added to the remaining process water. To destabilize the slurry system, a flocculant (polydiallyl dimethyl ammonium chloride (PDADMAC) from Sigma Aldrich, 60-80 cps viscosity, 20 wt% solids) was added to the slurry in the amounts shown in Table 9 to produce flocs.

[0274] After flocculation, the slurry was discharged through a single layer of wet-laid forming wire to produce a 30 cm x 30 cm blanket. The blanket and forming wire were then passed over a vacuum to remove additional water from the aerogel floes. The sample was compressed to a thickness of about 2 mm with a heavy roller to squeeze out some water and flatten the blanket to a consistent surface. All blankets were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes and then analyzed for room temperature thermal conductivity as described above. After drying, the blanket was compressed between two press plates to form a thin blanket 1-1.2 mm thick and then evaluated for tensile strength as described above. The total polymer loading was about 20% by weight and 11% by weight of the total solids in the slurry, excluding dispersants and defoamers. The resulting aerogel composition is expected to meet the standards of UL94-V0 rating.

[0275] Table 9

[0276]

[0277] Example 16

[0278] Experiments were conducted to evaluate the properties and / or performance of several nonwoven blankets. Glass microfibers (Microfiber B-06-F from Unifrax) were used in combination with 6 mm E-glass chopped strands having a diameter of 6 μm from Lauscha Fiber International in the amounts listed in Table 10.

[0279] The mat was produced in a wet-laid process according to the following procedure.

[0280] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (Nalco) and Foamkill were mixed according to the formulation in Table 10. TM830 defoamer (Crucible Chemical) was dispersed in water to form 3 liters (Example 16-1) or 2 liters (Example 16-2) of a white (process) aqueous dispersion. Mixing was performed under high shear for 10 seconds to form process water. After mixing, about 1.5 liters of process water were taken out from the Waring blender and retained. Chopped glass fibers were added to the WARING heavy-duty blender in the amounts listed in Table 10. The mixture in the blender was mixed under high shear (15000 rpm) for 40 seconds. ENTERAEV5400 aerogel particles (0.1-0.5 mm particle size, Cabot Corporation), glass microfibers, 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services) and aluminum trihydroxide (ATH, Thermo Fisher Scientific) were added to the blender and mixed under high shear for 40 seconds. A polyurethane binder (Joncryl FLX 5201 polyurethane from BASF) and a silicone binder (Dowsil HV 496 resin, Dow) were added to the blender and mixed under high shear for another 20 seconds to prepare a slurry, which was added to the retained process water. To destabilize the slurry system, a flocculant (polydiallyl dimethyl ammonium chloride (PDADMAC), 60-80 cps viscosity, 20 wt% solids, from Sigma Aldrich) was added to the slurry in the amounts shown in Table 10 to produce flocs.

[0281] After flocculation, the slurry was discharged through a single layer of wet-laid forming wire to produce a 30 cm×30 cm blanket. The blanket and forming wire were then passed over a vacuum to remove additional water from the aerogel flocculate. The samples were compressed to a thickness of about 1.8 mm (Example 16-1) and 1 mm (Example 16-2) with a heavy roller to squeeze out some water and flatten the blanket to a consistent surface. All blankets were removed from the forming wire and placed in a drying oven at 120° C. for about 20 minutes and then analyzed for room temperature thermal conductivity as described above. The tensile strength of Example 16-1 was evaluated without further compression. After drying, Example 16-2 was compressed between two press plates to form a thin blanket of about 0.55 mm thickness and then evaluated for tensile strength as described above. For both examples, the total polymer loading was about 22% by weight and 12% by weight of the total solids in the slurry, excluding dispersants and defoamers. The resulting aerogel composition is expected to meet the standards of UL94-V0 rating.

[0282] Table 10

[0283] Components (in grams) 16-1 16-2 Aerogel 9.54 6.36 Chopped Glass Fiber 1.14 0.76 Glass Microfiber 4.3 2.87 rutile sand 0.15 0.10 Silicon Carbide 1.38 0.92 ATH 1.00 0.67 Surfactants 1.76 1.17 Nalclear Polymers 1.98 1.32 Foamkill 1.76 1.17 PU adhesive 0.50 0.33 Silicone Adhesives 3.86 2.57 Flocculants 2.67 1.74 Tensile strength(MPa) 1.3 2.4 Thermal conductivity at 25°C (mW / mK) 25.4 24.5 <![CDATA[Density (g / cm 3 )]]> 0.21 0.53*

[0284] *Density measured after compression

[0285] Embodiment 17

[0286] Ceramic fiber ( 7001C5 ceramic fibers) were used in combination with 6 mm E-glass chopped fibers having a diameter of 6 μm from Lauscha Fiber International in the amounts listed in Table 11.

[0287] The mat was produced in a wet-laid process according to the following procedure.

[0288] In a WARING benchtop heavy duty blender, dispersant (Jeffamine M2070, Huntsman), Nalclear 71605 polymer (Nalco) and Foamkill were mixed according to the formulation in Table 11. TM 830 defoamer (Crucible Chemical) was dispersed in water to form one (1) liter of white (process) aqueous concentrate. Mixing was performed under high shear for 10 seconds to form process water. The concentrate was then diluted to about 3 liters of water. After mixing, about 1.5 liters of diluted process water were transferred to the Waring blender. Glass fiber, ENTERA EV5200 aerogel particles (Cabot Corporation), 44 micron rutile titanium dioxide sand (Loudwolf), F600 silicon carbide (Sturbridge Metallurgical Services) and aluminum trihydroxide (ATH, Thermo Fisher Scientific) were added to the WARING heavy duty blender in the amounts listed in Table 11. The mixture in the blender was mixed under high shear (15000 rpm) for 40 seconds. Ceramic fiber and epoxy binder (EPI-REZ 5003-W-55, 58% solids, Westlake) were added to the blender and mixed under high shear for another 20 seconds to prepare a slurry, which was added to the remaining process water. To destabilize the slurry system, a flocculant (polydiallyldimethylammonium chloride (PDADMAC), 60-80 cps viscosity, 20 wt% solids, from Sigma Aldrich) was added to the slurry until flocs appeared.

[0289] After flocculation, the slurry was discharged through a single layer of wet-laid forming wire to produce a 30 cm x 30 cm blanket. The blanket and forming wire were then passed over a vacuum to remove additional water from the aerogel floes. The samples were compressed to a thickness of about 4 mm (Example 17-1) or 6 mm (Example 17-2) with a heavy roller to squeeze out some of the water and flatten the blanket to a consistent surface. All blankets were removed from the forming wire and placed in a drying oven at 120°C for about 20 minutes. The total polymer loading was about 20% of the total solids in the slurry. The resulting aerogel composition is expected to have a thermal conductivity of less than 25 or 30 mW / mK and a tensile strength of greater than 0.1 or 0.2 MPa, and meet the standards of UL94-V0 rating.

[0290] Table 11

[0291] Components (in grams) 17-1(4mm) 17-2(6mm) Aerogel 21.86 32.79 Ceramic Fiber 9.1 13.65 Fiberglass 1.82 2.73 rutile sand 2.76 4.14 Silicon Carbide 2.76 4.14 ATH 0.88 1.32 Surfactants 3.52 5.28 Nalclear Polymers 3.97 5.95 Foamkill 3.52 5.28 Epoxy Adhesives 5.84 8.76

[0292] While the invention has been particularly shown and described with reference to preferred embodiments thereof, it will be understood by those skilled in the art that various changes in form and details may be made without departing from the scope of the invention as encompassed by the following claims.

Claims

1. An aerogel composition comprising: Aerogel particles; A fibrous component comprising one or more materials selected from polymer fibers and inorganic fibers, wherein the weight ratio of aerogel particles:fibrous component is 1:3-10:1; and 3 to 25% by weight of a polymer, based on the total weight of the composition, The composition has a thickness of 0.3-6 mm, a thermal conductivity of up to 32 mW / mK at 25° C., a UL-94 rating of V0, a ​​tensile strength of 0.09-5 MPa, and a 3 density.

2. The composition according to claim 1, wherein the aerogel particles are silica aerogel particles.

3. The composition of claim 2, wherein the silica aerogel particles are hydrophobic.

4. The composition of any one of claims 1-3, wherein the composition comprises 15-65 wt% aerogel particles, for example, 20-60 wt%, 25-55 wt%, 30-50 wt%, or 35-45 wt%.

5. The composition of any one of claims 1-4, wherein the aerogel particles have a particle size in the range of 0.1 mm-5 mm, for example, 0.1 mm-4 mm, 0.1 mm-1.5 mm, or 1 mm-4 mm.

6. The composition of any one of claims 1-5, wherein the weight ratio of aerogel particles:fibrous component is 1:2-10:1, 1:3-3:1, 1:2-2:1, 1.2:1-9:1, 1:2-7:1, or 1:1-5:

1.

7. The composition of any one of claims 1-6, wherein the fibrous component is present in an amount of 5-55 wt%, for example, 10-50 wt%, 15-40 wt%, 20-35 wt%, or 10-30 wt%.

8. The composition of any one of claims 1-7, wherein the fibrous component comprises glass fibers, ceramic fibers, or both.

9. The composition of any one of claims 1-8, wherein the fibrous component comprises a blend of primary fibers and one or more secondary fibers.

10. The composition of claim 9, wherein the primary fiber comprises glass fiber or ceramic fiber, and the secondary fiber is selected from ceramic wool, glass fiber, ceramic fiber, aramid fiber, PBI fiber, cellulose fiber, cotton fiber, carbon fiber, acrylic fiber, polyvinyl alcohol (PVA) fiber, phenolic fiber, polyolefin fiber, and any mixture of the former.

11. The composition of claim 9 or 10, wherein the secondary fibers are selected from the group consisting of ceramic wool, glass fibers, ceramic fibers, aramid fibers, and PBI fibers.

12. The composition of any one of claims 9-11, wherein the primary fibers and the secondary fibers differ in at least one of aspect ratio, length, length distribution, diameter, diameter distribution, and composition.

13. The composition of any one of claims 9-12, wherein the primary fibers are present in the composition in a greater proportion than the secondary fibers.

14. The composition of any one of claims 9-13, wherein the weight ratio of the primary fiber to the secondary fiber is 100: 1-1: 100, for example, 50: 1-1:50, 35: 1-1:35, 25: 1-1:25, 15: 1-1:15, 10: 1-1:10, 7: 1-1:7, 5: 1-1:5, 4: 1-1:4, 3: 1-1:3, or 2: 1-1:

2.

15. The composition according to any one of claims 1 to 14, having a thermal conductivity of 5 mW / m·K to 32 mW / m·K at 25°C, for example, 10 mW / m·K to 30 mW / m·K, 17 mW / m·K to 25 mW / m·K, or 15 mW / m·K to 25 mW / m·K.

16. The composition of any one of claims 1-15, further comprising a sunscreen.

17. The composition of claim 16, wherein the sunscreen is selected from carbon black, mica, alumina, graphite, titanium dioxide, rutile sand, iron oxide, silicon carbide (SiC), graphite, zirconium dioxide, and combinations of two or more of these.

18. A composition according to claim 16 or 17, wherein the sunscreen is present in an amount of up to 10 wt%, for example, 0.5 wt%-8 wt%, 0.75 wt%-5 wt%, or 1 wt%-3 wt%.

19. The composition of any one of claims 1-18, wherein the composition has a thickness of 0.3-6 mm, for example, 0.4-4 mm, 1-3 mm, or 1.5-2.5 mm.

20. The composition of any one of claims 1-19, wherein the composition has a tensile strength of 0.1-3 MPa or 0.15-2 MPa.

21. The composition of any one of claims 1-20, further comprising one or more of a flame retardant, a flame retarder, an endothermic material, or a phase change material.

22. The composition according to any one of claims 1 to 21, having a molecular weight of 0.1 to 0.6 g / cm 3 Density, for example, 0.15-0.5 g / cm 3 , 0.15-0.4g / cm 3 , or 0.2-0.35g / cm 3 .

23. The composition of any one of claims 1-22, wherein the polymer comprises a surfactant, a dispersant, or both.

24. The composition of claim 23, wherein the surfactant or dispersant is selected from ionic (anionic and cationic) surfactants and dispersants, amphoteric surfactants and dispersants, nonionic surfactants and dispersants, and high molecular weight surfactants and dispersants.

25. A composition according to claim 23 or 24, wherein the dispersant is a cationic dispersant, for example having an HLB ratio of 2-20.

26. The composition of any one of claims 23-25, wherein the cationic dispersant comprises ethylene oxide and propylene oxide oligomers having a molar ratio of ethylene oxide units to propylene oxide units of 0.1:1 to 11:

1.

27. The composition of any one of claims 1-26, wherein the polymer comprises a binder.

28. The composition of claim 27, wherein the binder is selected from silicone, polyurethane, polyvinyl alcohol, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, styrene-butadiene copolymer, and acrylate (acrylic) polymers.

29. The composition of claim 27 or 28, wherein the adhesive is selected from acrylic polymers, silicones, polyurethanes, and combinations of two or more of these.

30. A composition according to any one of claims 1 to 29, wherein Based on the total weight of the composition, the weight proportion of the polymer is 4-20%, 5-10%, 10-15%, 15-20%, 20-25%, 5%-15%, or 8%-17%.

31. The composition of any one of claims 1-30, further comprising elastomeric particles.

32. The composition of claim 1, wherein the polymer comprises a flocculation system comprising a flocculant and a flocculating polymer.

33. The composition of claim 31 , wherein the flocculant is polymeric.

34. The composition according to claim 31 or 32, wherein a) the flocculant is cationic and the flocculant polymer is anionic, or, b) the flocculant is anionic and the flocculant polymer is cationic.

35. A composition according to any one of claims 1 to 34, wherein the polymer comprises a flocculation system comprising a flocculant and a flocculating polymer, an optional binder, a dispersant, and an optional defoamer, wherein the total amount of the flocculation system and the optional binder in the composition is 3 to 20 wt%, such as 4 to 16 wt%.

36. The composition of any one of claims 1-35, wherein the composition is self-supporting.

37. A method of making a nonwoven aerogel composition, the method comprising: mixing aerogel particles, a fibrous component, at least one polymeric component, and an aqueous solvent to form an aqueous slurry, wherein the weight ratio of aerogel particles:fibrous component is 1:3-10:1; flocculating and / or coagulating the aqueous slurry to form a floc comprising the aerogel particles, the fibrous component, at least a portion of the polymeric component, and a supernatant; Dewatering the flocs; and The flocculates are dried to produce the nonwoven aerogel composition having a thickness of 0.3-6 mm, a thermal conductivity of up to 32 mW / mK at 25° C., a UL-94 rating of V0, a ​​tensile strength of 0.09-5 MPa, and a strength of 0.1-0.6 g / cm 3 The density of The total amount of the polymeric components in the floccules and the supernatant is 3-25% based on the total amount of materials in the floccules and the supernatant except the aqueous solvent.

38. The method of claim 37, wherein the aqueous solvent comprises less than 5 wt% organic solvent, for example, less than 3 wt% or less than 1 wt%.

39. The method of claim 37 or 38, wherein the total amount of solid material including the polymeric component in the aqueous slurry is 5 wt%-25 wt%, for example, 5-10 wt%, 10-15 wt%, 15-20 wt%, or 20-25 wt%.

40. The method of any one of claims 37-39, further comprising compressing the dewatered floc.

41. The method of any one of claims 37-40, further comprising compressing the nonwoven aerogel blanket.

42. The method of any one of claims 37-41, wherein the aerogel particles are silica aerogel particles.

43. The method of claim 42, wherein the silica aerogel particles are hydrophobic.

44. The method of any one of claims 37-43, wherein the total amount of aerogel particles in the flocs and the supernatant is 15-65 wt%, such as 20-60 wt%, 25-55 wt%, 30-50 wt%, or 35-45 wt%, excluding the aqueous solvent.

45. The method of any one of claims 37-44, wherein the aerogel particles have a particle size in the range of 0.1 mm-5 mm, for example, 0.1 mm-4 mm, 0.1 mm-1.5 mm, or 1 mm-4 mm.

46. ​​The method of any one of claims 37-45, wherein the weight ratio of aerogel particles:fibrous component is 1:2-10:1, 1:3-3:1, 1:2-2:1, 1.2:1-9:1, 1:2-7:1, or 1:1-5:

1.

47. The method of any one of claims 37-46, wherein the fibrous component is present in the floc and the supernatant in an amount of 5-55 wt%, such as 10-50 wt%, 15-40 wt%, 20-35 wt%, or 10-30 wt%, excluding the aqueous solvent.

48. The method of any one of claims 37-47, wherein the fibrous component comprises glass fibers, ceramic fibers, or both.

49. The method of any one of claims 37-48, wherein the fibrous component comprises a blend of primary fibers and one or more secondary fibers.

50. The method of claim 49, wherein the primary fiber comprises glass fiber or ceramic fiber, and the secondary fiber is selected from ceramic wool, glass fiber, ceramic fiber, aramid fiber, PBI fiber, cellulose fiber, cotton fiber, carbon fiber, acrylic fiber, polyvinyl alcohol (PVA) fiber, phenolic fiber, polyolefin fiber, and any mixture of the former.

51. The method of claim 49 or 50, wherein the secondary fibers are selected from the group consisting of ceramic wool, glass fibers, ceramic fibers, aramid fibers, and PBI fibers.

52. The method of any one of claims 49-51, wherein the primary fibers and the secondary fibers differ in at least one of aspect ratio, length, length distribution, diameter, diameter distribution, and composition.

53. The method of any one of claims 49-52, wherein the primary fibers are present in the composition in a greater proportion than the secondary fibers.

54. The method of any one of claims 49-53, wherein the weight ratio of the primary fiber to the secondary fiber is 100:1-1:100, for example, 50:1-1:50, 35:1-1:35, 25:1-1:25, 15:1-1:15, 10:1-1:10, 7:1-1:7, 5:1-1:5, 4:1-1:4, 3:1-1:3, or 2:1-1:

2.

55. The method of any one of claims 37-54, wherein the nonwoven aerogel composition has a thermal conductivity at 25°C of 5 mW / m·K to 32 mW / m·K, for example, 10 mW / m·K to 30 mW / m·K, 17 mW / m·K to 25 mW / m·K, or 15 mW / m·K to 25 mW / m·K.

56. The method of any one of claims 37-55, wherein mixing further comprises including an opacifier in the aqueous slurry.

57. The method of claim 56, wherein the opacifier is selected from carbon black, mica, aluminum oxide, graphite, titanium dioxide, rutile sand, iron oxide, silicon carbide (SiC), graphite, zirconium dioxide, and combinations of two or more of these.

58. A method according to claim 56 or 57, wherein the sunscreen is present in the flocculent and supernatant in an amount of up to 10 wt%, such as 0.5 wt%-8 wt%, 0.75 wt%-5 wt%, or 1 wt%-3 wt%, excluding the aqueous solvent.

59. The method of any one of claims 37-58, wherein the nonwoven aerogel composition has a thickness of 0.3-6 mm, for example, 0.4-4 mm, 1-3 mm, or 1.5-2.5 mm.

60. The method of any one of claims 37-59, wherein the nonwoven aerogel composition has a tensile strength of 0.1-3 MPa or 0.15-2 MPa.

61. The method of any one of claims 37-60, wherein mixing further comprises including one or more of a flame retardant, a flame retarder, an endothermic material, or a phase change material in the aqueous slurry.

62. The method of any one of claims 37-61, wherein the nonwoven aerogel composition has a thickness of 0.1-0.6 g / cm 3 Density, for example, 0.15-0.5 g / cm 3 , 0.15-0.4g / cm 3 , or 0.2-0.35g / cm 3 .

63. The method of any one of claims 37-62, wherein the polymeric component comprises a surfactant, a dispersant, or both.

64. The method of claim 63, wherein the surfactant or dispersant is selected from ionic (anionic and cationic) surfactants and dispersants, amphoteric surfactants and dispersants, nonionic surfactants and dispersants, and high molecular weight surfactants and dispersants.

65. A method according to claim 63 or 64, wherein the dispersant is a cationic dispersant, for example, having an HLB ratio of 2-20.

66. The method of any one of claims 63-65, wherein the cationic dispersant comprises ethylene oxide and propylene oxide oligomers having a molar ratio of ethylene oxide units to propylene oxide units of 0.1:1 to 11:

1.

67. The method of any one of claims 37-66, wherein the polymeric component further comprises a defoaming agent.

68. The method of any one of claims 37-67, wherein the polymeric component comprises a binder.

69. The method of claim 68, wherein the adhesive is selected from silicone, polyurethane, polyvinyl alcohol, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, styrene-butadiene copolymer, and acrylate (acrylic) polymers.

70. The method of claim 68 or 69, wherein the adhesive is selected from acrylic polymers, silicones, polyurethanes, and combinations of two or more of these.

71. The method of any one of claims 37-70, wherein the weight ratio of the polymeric components in the floccules and the supernatant is 4-20%, 5-10%, 10-15%, 15-20%, 20-25%, 5%-15%, or 8%-17%, excluding the aqueous solvent.

72. The method of any one of claims 37-71, wherein mixing further comprises including elastomeric particles in the aqueous slurry.

73. The method of any one of claims 37-72, wherein one or more of flocculation or coagulation comprises adding a flocculant to the aqueous slurry.

74. The method of claim 73, wherein the flocculant is polymeric.

75. The method of any one of claims 37-74, wherein: The polymeric component comprises a flocculating polymer and wherein a) the flocculating agent is cationic and the flocculating polymer is anionic or b) the flocculating agent is anionic and the flocculating polymer is cationic.

76. A method according to claim 75, wherein the total amount of flocculant, flocculating polymer and optional binder in the floc and supernatant is 3-20 wt%, such as 4-16 wt%, excluding the aqueous solvent.

77. The method of any one of claims 37-76, wherein the nonwoven aerogel composition is self-supporting.

78. The method of any one of claims 37-77, further comprising coating the dried aerogel composition with a polymer or oligomer solution or emulsion and curing the solution or emulsion to form a coating on the aerogel composition.

79. The method of claim 78, wherein the coating comprises polyolefins, silicone polymers, polyvinyl alcohol, starch, polytetrafluoroethylene, phenolic polymers, melamine polymers, phenol formaldehyde, and acrylic polymers.

80. The method of any one of claims 37-79, further comprising treating the aerogel composition with a hydrophobic agent.

81. The method of claim 80, wherein the hydrophobic agent is selected from a silane compound, a silazane compound, or a disiloxane compound.

82. The method of claim 80 or 81, wherein: The hydrophobic agent is selected from trimethylchlorosilane, dimethyldichlorosilane, hexamethyldisilazane and hexamethyldisiloxane.

83. An aerogel composition obtained by the method according to any one of claims 37-82.

84. A thermal control article comprising the aerogel composition of any one of claims 1-37 and 83.

85. The thermal control article of claim 84, wherein the article is a blanket, a sheet, a felt, or a mat.

86. A thermal control article according to claim 84 or 85, wherein the article is a flexible nonwoven blanket.

87. The thermal control article of any one of claims 84-86 having a non-flammable flammability rating according to UL94-V0.

88. The thermal control article of any one of claims 84-87, having a thermal conductivity at 25°C of up to 30 mW / mK.

89. The thermal control article of any one of claims 84-88, having a thermal conductivity at 25°C of 5mW / m·K-30mW / m·K, for example, 17mW / m·K-30mW / m·K or 15mW / m·K-25mW / m·K.

90. The thermal control article of any one of claims 84-89, having a tensile strength of 0.09-5 MPa, for example, 0.1-3 MPa or 0.15-2 MPa.

91. The thermal control article of any one of claims 84-90, comprising a plurality of stacked layers of the aerogel composition.

92. The thermal control article of any one of claims 84-91, further comprising one or more layers independently comprising a woven polymer felt, a foam pad, a mica sheet, or a thermally conductive material.

93. The thermal control article of any one of claims 84-92, wherein at least one surface of the thermal control article is covered by a polymer film.

94. The thermal control article of claim 93, wherein the polymer is selected from the group consisting of silicone polymers, polyvinylidene fluoride, polyethylene terephthalate, and chlorinated polyethylene.

95. The thermal control article of claim 93 or 94, wherein the polymer film comprises reinforcing fibers.

96. The thermal control article of any one of claims 84-95, further comprising a coating.

97. The thermal control article of claim 96, wherein the coating comprises polyolefins, silicone polymers, polyvinyl alcohol, starch, polytetrafluoroethylene, phenolic polymers, melamine polymers, phenol formaldehyde, and acrylic polymers.

98. An electric vehicle comprising a thermal control article according to any one of claims 84-97.

99. A battery comprising the thermal management article of any one of claims 84-97.

Citation Information

Patent Citations

  • Heat insulation sheet for assembled batteries and assembled battery

    EP3835262A1

  • Heat insulating body and heater

    JP2012145204A

  • Fiber substrate and heat insulation mat including fiber substrate

    JP2015048543A

  • Aerogel composite and manufacturing method therefor

    JP2020019925A

  • Aerogel-containing composition and insulation blanket prepared using the same

    US10640629B2